Transparent laminate

JP2025026962AActive Publication Date: 2025-02-26NIPPON SHEET GLASS CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2024202464
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-06-09
Filing Date
2024-11-20
Publication Date
2025-02-26
Estimated Expiration
2040-12-25

AI Technical Summary

Benefits of technology

【0081】 本発明によれば、基板の表面に透明の機能層が積層されているため、この機能層に機能を持たせることで、物品の保護以外の用途にも用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026962000001_ABST
    Figure 2025026962000001_ABST
Patent Text Reader

Abstract

To provide a cover member also usable for a purpose other than protection of an article.SOLUTION: A cover member includes: a transparent substrate having a first principal plane and a second principal plane; and a transparent first functional layer laminated on the first principal plane of the substrate.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent laminate. [Background technology]

[0002] 2. Description of the Related Art Transparent substrates such as glass plates and resin plates are used for various purposes, and for example, are sometimes used as cover members for protecting articles (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-144575 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, such cover members are required to have functions other than simply protecting articles. The present invention has been made to solve the above problems, and has an object to provide a cover member that can be used for purposes other than protecting articles. [Means for solving the problem]

[0005] Item 1. A transparent substrate having a first main surface and a second main surface; A transparent first functional layer laminated on a first main surface of the substrate; A transparent laminate comprising:

[0006] Item 2. The transparent laminate according to item 1, wherein the first functional layer has an antifogging function.

[0007] Item 3. The transparent laminate according to item 1 or 2, wherein the first functional layer has a surface roughness Ra of 1 to 1000 nm.

[0008] Item 4. The first functional layer is A base film having a first main surface and a second main surface; An adhesive layer laminated on the second main surface of the base film; An anti-fogging layer laminated on a first main surface of the substrate film; Equipped with Item 4. The transparent laminate according to any one of items 1 to 3, wherein the base film is fixed to the first main surface of the substrate via the adhesive layer.

[0009] Item 5. The first functional layer includes an adhesive layer and an anti-fogging layer, Item 4. The transparent laminate according to any one of items 1 to 3, wherein the anti-fogging layer is fixed to the first main surface of the substrate via the adhesive layer.

[0010] Item 6. The first functional layer has an anti-fogging layer, Item 4. The transparent laminate according to any one of items 1 to 3, wherein the antifogging layer is laminated on a first main surface of the substrate.

[0011] Item 7. The transparent laminate according to any one of Items 4 to 6, wherein the antifogging layer has a moisture absorbing layer containing a moisture absorbing resin material.

[0012] Item 8. The anti-fogging layer includes the moisture absorbing layer and a hydrophilic layer laminated on the moisture absorbing layer and having hydrophilicity. Item 8. The transparent laminate according to item 7,

[0013] Item 9. The transparent laminate according to item 8, wherein the hydrophilic layer of the antifogging layer contains a polyether-modified dimethylsiloxane represented by the following formula (A): [ka] where m is an integer of 2 or more, n, x, and y are independently integers of 1 or more, R 1 is a hydrogen atom or a methyl group, R 2 is an alkyl group having 1 to 3 carbon atoms.

[0014] Item 10. In the formula (A), m is an integer from 1 to 3, n is an integer between 3 and 600, y / (x+y) is 0.01 or more and less than 1, Item 10. The transparent laminate according to item 9, having an average molecular weight of 3,000 to 300,000.

[0015] Item 11. The transparent laminate according to item 7, wherein in the antifogging layer, a hydrophilizing agent is dispersed in the moisture absorbing layer.

[0016] Item 12. The transparent laminate according to item 11, wherein the antifogging layer contains a solvent having a boiling point of 100° C. or more and 300° C. or less.

[0017] Item 13. The transparent laminate according to item 12, wherein the solvent has an alcohol group.

[0018] Item 14. The transparent laminate according to any one of Items 11 to 13, wherein the anti-fogging layer has anti-fogging properties after being abraded a predetermined number of times with a cloth soaked in alcohol.

[0019] Item 15. The transparent laminate according to any one of Items 11 to 14, wherein the anti-fogging layer has anti-fogging properties after a predetermined constant temperature and humidity test.

[0020] Item 16. The transparent laminate according to any one of Items 11 to 15, wherein the antifogging layer is formed of a single layer.

[0021] Item 17. The transparent laminate according to any one of Items 1 to 6, wherein the first functional layer is mainly composed of an inorganic compound.

[0022] Item 18. Visible light transmittance is 85% or more, Item 18. The transparent laminate according to item 17, having a visible light reflectance of 10% or less.

[0023] Item 19. The transparent laminate according to item 17 or 18, wherein the minimum transmittance in the visible light wavelength range is within 5% of the transmittance of the substrate.

[0024] Item 20. The transparent laminate according to any one of Items 17 to 19, wherein the maximum reflectance in the visible light wavelength range is within 5% of the reflectance of the substrate.

[0025] Item 21. Reflectance in the visible light wavelength range: 21. The transparent laminate according to any one of items 17 to 20, wherein 1≦maximum reflectance / minimum reflectance≦1.5 is satisfied.

[0026] Item 22. The transparent laminate according to any one of Items 17 to 21, wherein the first functional layer contains inorganic fine particles and an inorganic binder.

[0027] Item 23. The transparent laminate according to item 22, wherein the film thickness of the first functional layer is not more than twice the particle diameter of the inorganic fine particles.

[0028] Item 24. The transparent laminate according to item 22 or 23, wherein the inorganic fine particles are made of SiO2.

[0029] Item 25. The transparent laminate according to item 24, wherein the SiO2 content in the first functional layer is 28 mass% or less.

[0030] Item 26. The transparent laminate according to any one of Items 22 to 25, wherein the first functional layer contains photocatalytic fine particles.

[0031] Item 27. The transparent laminate according to item 26, wherein the photocatalyst particles are formed of an oxide or oxynitride containing titanium, tungsten, or iron as a main component.

[0032] Item 28. The transparent laminate according to item 26 or 27, wherein the content of the photocatalyst particles is 40 mass % or less.

[0033] Item 29. The transparent laminate according to any one of Items 26 to 28, wherein the content of the inorganic binder is 30% by mass or more.

[0034] Item 30. The transparent laminate according to any one of Items 17 to 29, wherein the first functional layer has anti-fogging properties after being immersed in water for a predetermined period of time.

[0035] Item 31. A transparent laminate according to any one of Items 17 to 30, wherein the first functional layer has anti-fogging properties after being abraded a predetermined number of times with a cloth soaked in alcohol.

[0036] Item 32. A transparent laminate according to any one of Items 17 to 31, wherein the first functional layer is abraded a predetermined number of times with a cloth soaked in alcohol and then irradiated with ultraviolet light, so that the first functional layer has anti-fogging properties.

[0037] Item 33. The transparent laminate according to any one of Items 17 to 32, wherein the first functional layer has anti-fogging properties when irradiated with ultraviolet light after a predetermined constant temperature and humidity test.

[0038] Item 34. The transparent laminate according to any one of items 17 to 33, which is used as a cover member for a surveillance camera that is placed outdoors.

[0039] Item 35. The transparent laminate according to item 34, wherein the surveillance camera is equipped with an ultraviolet irradiation device.

[0040] Item 36. The transparent laminate according to item 34 or 35, wherein the first functional layer is arranged to face the surveillance camera.

[0041] Item 37. The transparent laminate according to item 34, wherein the first functional layer is arranged to face away from the surveillance camera.

[0042] Item 38. A transparent laminate according to any one of items 2 to 10, further comprising a second functional layer laminated on the first functional layer and having moisture permeability.

[0043] Item 39. The first functional layer is formed of an organic-inorganic composite material; Item 39. The transparent laminate according to item 38, wherein the refractive index of the second functional layer is smaller than that of the first functional layer.

[0044] Item 40. The transparent laminate according to item 38 or 39, wherein the second functional layer is a single layer.

[0045] Item 41. The transparent laminate according to item 40, wherein the second functional layer has a refractive index of 1.10 to 1.45.

[0046] Item 42. The transparent laminate according to item 41, wherein when the refractive index of the first functional layer is X, the refractive index of the second functional layer is √X±0.1.

[0047] Item 43. The transparent laminate according to item 42, wherein the second functional layer contains hollow particles and a binder that binds the hollow particles.

[0048] Item 44. The transparent laminate according to item 43, wherein the hollow particles have a refractive index of 1.15 to 2.70.

[0049] Item 45. The transparent laminate according to item 43 or 44, wherein the hollow particles have an average particle size of 20 to 100 nm.

[0050] Item 46. The transparent laminate according to any one of Items 43 to 45, wherein the hollow particles are selected from the group consisting of silica, magnesium fluoride, alumina, aluminosilicate, titania, and zirconia.

[0051] Item 47. A transparent laminate according to any one of Items 38 to 46, wherein the second functional layer contains a solvent having a boiling point of 100° C. or more and 300° C. or less.

[0052] Item 48. The transparent laminate according to item 47, wherein the solvent is mainly composed of 3-methoxy-3-methyl-1-butanol.

[0053] Item 49. The second functional layer contains the solvent at 1 ppb or more and 5 g / cm 3 Contains the following: 7 or 48. A transparent laminate according to claim 7 or 48.

[0054] Item 50. The transparent laminate according to any one of Items 43 to 49, wherein the binder contains at least one of polysilsesquioxane and silica.

[0055] Item 51. The transparent laminate according to any one of Items 43 to 50, wherein the second functional layer has a void ratio of 0 to 70 vol %.

[0056] Item 52. The transparent laminate described in Item 38 or 39, wherein the second functional layer comprises a first layer laminated on the first functional layer, and a second layer laminated on the first layer and having a lower refractive index than the first layer.

[0057] Item 53. The refractive index of the first layer is 1.35 to 1.55; Item 53. The transparent laminate according to item 52, wherein the second layer has a refractive index of 1.10 to 1.25.

[0058] Item 54. The transparent laminate according to item 53, wherein the second layer contains hollow particles and a binder that binds the hollow particles.

[0059] Item 55. The transparent laminate according to item 54, wherein the hollow particles have a refractive index of 1.15 to 2.70.

[0060] Item 56. The transparent laminate according to item 54 or 55, wherein the hollow particles have an average particle size of 20 to 100 nm.

[0061] Item 57. The transparent laminate according to any one of Items 54 to 56, wherein the hollow particles are selected from the group consisting of silica, magnesium fluoride, alumina, aluminum silicate, titania, and zirconia.

[0062] Item 58. The transparent laminate according to any one of items 54 to 57, wherein the binder contains at least one of polysilsesquioxane and silica.

[0063] Item 59. The transparent laminate according to any one of items 54 to 58, wherein the second layer has a void ratio of 0 to 70 vol%.

[0064] Item 60. The transparent laminate according to any one of items 54 to 59, wherein the first layer contains the binder of the second layer.

[0065] Item 61. The transparent laminate according to any one of items 38 to 60, wherein the second functional layer has a flexural modulus of 1 to 10 GPa.

[0066] Item 62. A transparent laminate according to any one of items 38 to 61, wherein the flexural modulus of the second functional layer overlaps with the flexural modulus of the first functional layer.

[0067] Item 63. The transparent laminate according to any one of Items 38 to 62, wherein the difference between the linear expansion coefficient of the first functional layer and the linear expansion coefficient of the second functional layer is 50 ppm / ° C. or less.

[0068] Item 64. The transparent laminate according to item 1, wherein the first functional layer has an anti-reflection function.

[0069] Item 65. The transparent laminate according to item 64, wherein the first functional layer is formed of a film in which an adhesive layer, a base sheet, and an anti-reflection layer are laminated in this order.

[0070] Item 66. The transparent laminate according to item 65, wherein the refractive index of the antireflection layer of the first functional layer is 1.10 to 1.45.

[0071] Item 67. The transparent laminate according to item 65 or 66, wherein the antireflection layer of the first functional layer contains hollow particles and a binder that binds the hollow particles.

[0072] Item 68. The transparent laminate according to item 67, wherein the hollow particles have a refractive index of 1.15 to 2.70.

[0073] Item 69. The transparent laminate according to item 67 or 68, wherein the hollow particles have an average particle size of 20 to 100 nm.

[0074] Item 70. The transparent laminate according to any one of Items 65 to 69, wherein the antireflection layer contains a second solvent having a boiling point higher than that of water and lower than the heat resistance temperature of the substrate.

[0075] Item 71. The transparent laminate according to item 70, wherein the second solvent is mainly composed of 3-methoxy-3-methyl-1-butanol.

[0076] Item 72. The first functional layer contains the second solvent at a concentration of 1 ppb or more and 5 g / cm 3 Item 70 or 71. The transparent laminate according to item 70 or 71, wherein the transparent laminate contains no more than 1,0 ... methyl ethyl ether.

[0077] Item 73. The transparent laminate according to any one of items 2 to 72, wherein the substrate is glass.

[0078] Item 74. The transparent laminate according to any one of Items 2 to 73, wherein the substrate is float glass produced by a float process, and the concentration of tin oxide in the first main surface is lower than the concentration of tin oxide in the second main surface.

[0079] Item 75. The transparent laminate according to any one of Items 2 to 73, wherein the substrate is float glass produced by a float process, and the concentration of tin oxide in the first main surface is higher than the concentration of tin oxide in the second main surface.

[0080] Item 76. A transparent laminate according to any one of items 1 to 75, further comprising a third functional layer laminated on the second main surface of the substrate. Effect of the Invention

[0081] According to the present invention, since a transparent functional layer is laminated on the surface of the substrate, by imparting a function to this functional layer, it can be used for purposes other than protecting articles. [Brief description of the drawings]

[0082] [Figure 1] 1 is a cross-sectional view showing a first embodiment of a cover member according to the present invention. [Diagram 2] It is a schematic diagram showing an example in which a cover member is provided in front of the lens of the imaging device. [Diagram 3] It is a schematic diagram showing an example in which a cover member is provided in front of the lens of the imaging device housed in the housing. [Figure 4] It is a graph showing Examples 1 to 3 and the transmittance of the base material. [Diagram 5] It is a graph showing Examples 1 to 3 and the reflectance of the base material. [Figure 6] It is a cross-sectional view showing a second embodiment of the cover member according to the present invention. [Figure 7] It is a cross-sectional view showing a schematic configuration of a second functional layer as an antireflection layer. [Figure 8] It is a cross-sectional view showing another example of the cover member of the second embodiment. [Figure 9] It is a cross-sectional view showing another example of the cover member of the second embodiment. [Figure 10] It is a cross-sectional view showing another example of the cover member of the second embodiment. [Figure 11] It is a graph showing the single-sided reflectance of Examples 23 and 26. [Figure 12] It shows the single-sided reflectance of 400 to 700 nm of the film on which the antireflection film of Examples 28 to 30 is formed.

Mode for Carrying Out the Invention

[0083] <A. First Embodiment> Hereinafter, a first embodiment when the transparent laminate according to the present invention is applied to a cover member will be described with reference to the drawings. FIG. 1 is a cross-sectional view of the cover member.

[0084] <1. Outline of the cover member> As described later, the cover member according to this embodiment is disposed in front of the lens of an imaging device such as a camera to protect the lens, etc. Specifically, as shown in Fig. 1, this cover member 10 has a transparent base material 1 having a first main surface 11 and a second main surface 12, and a first functional layer 2 laminated on the first main surface 11 of this base material 1. Each member will be described in detail below.

[0085] <2. Base material> The substrate 1 can be formed of a resin material (organic polymer material) having light-transmitting properties or a glass plate. The shape of the substrate is not particularly limited, and can be a circular shape, a rectangular shape, a polygonal shape, an irregular shape, or the like, and can be appropriately determined according to various applications as described below. Specific examples will be described below.

[0086] <2-1. Resin materials> The resin material is not particularly limited as long as it has the above-mentioned light-transmitting properties, but may be, for example, polycarbonate (PC), acrylonitrile / styrene resin (AS), acrylonitrile / butadiene / styrene resin (ABS), methacrylic resin (PMMA), polyvinyl chloride (PVC), triacetyl cellulose (TAC), etc., or a material containing a combination of these.

[0087] <2-2. Glass plate> There is no particular limitation on the glass plate 1, and any known transparent glass plate can be used. For example, various glass plates such as float glass, heat absorbing glass, clear glass, green glass, UV green glass, and soda lime glass can be used.

[0088] Examples of compositions of clear glass, heat absorbing glass, soda-lime glass, and float glass are shown below.

[0089] <2-2-1. Clear glass> SiO2:70~73% by mass Al2O3:0.6~2.4% by mass CaO: 7~12% by mass MgO: 1.0~4.5% by mass RO: 13 to 15 mass% (R is an alkali metal) Total iron oxide converted to Fe2O3 (T-Fe2O3): 0.08-0.14 mass%

[0090] <2-2-2.Heat absorbing glass> The composition of the heat ray absorbing glass can be, for example, based on the composition of clear glass, with the ratio of total iron oxide converted to Fe2O3 (T-Fe2O3) being 0.4 to 1.3 mass%, the ratio of CeO2 being 0 to 2 mass%, the ratio of TiO2 being 0 to 0.5 mass%, and the glass skeletal components (mainly SiO2 and Al2O3) being reduced by the increases in T-Fe2O3, CeO2, and TiO2.

[0091] <2-2-3. Soda-lime glass> SiO2: 65~80% by mass Al2O3: 0~5% by mass CaO: 5~15% by mass MgO: 2% by mass or more NaO: 10~18% by mass K2O: 0~5% by mass MgO+CaO: 5~15% by mass Na2O+K2O: 10~20% by mass SO3:0.05~0.3% by mass B2O3:0~5% by mass Total iron oxide converted to Fe2O3 (T-Fe2O3): 0.02-0.03 mass%

[0092] <2-2-4. Float glass> SiO265~80% Al2O30-5% MgO 0~20% CaO 0~20% Na2O 10~20% K2O 0~5%

[0093] <2-2-4-1. Highly transparent float glass> SiO2 66~72% Al2O3 2~4% MgO 8~15% CaO 1~8% Na2O 12~16% K2O 0~1% Including, MgO+CaO is in the range of 12-17%. Molar ratio CaO / (MgO+CaO) is 0.1-0.4

[0094] Each component constituting the composition of this float glass will be described below. (SiO2) SiO2 is a major component constituting the glass plate 1, and if the content is too low, the chemical durability such as water resistance and heat resistance of the glass are reduced. On the other hand, if the SiO2 content is too high, the viscosity of the glass plate 1 at high temperatures increases, making it difficult to melt and mold. Therefore, the SiO2 content is appropriately in the range of 66 to 72 mol%, and preferably 67 to 70 mol%.

[0095] (Al2O3) Al2O3 is a component that improves the chemical durability of the glass sheet 1, such as its water resistance, and also increases the surface compressive stress after chemical strengthening by facilitating the movement of alkali metal ions in the glass, and deepens the depth of the stress layer. On the other hand, if the content of Al2O3 is too high, it increases the viscosity of the molten glass, increasing T2 and T4, and also impairing the clarity of the molten glass, making it difficult to manufacture high-quality glass sheets. In the float process, the working temperature is set at a temperature of 10°C or lower when the glass viscosity is 10°C. 4 The melting temperature is the temperature at which the glass viscosity becomes 10 2 This is the temperature at which the viscosity becomes dPa·s, hereafter referred to as T2.

[0096] Therefore, the Al2O3 content is suitably in the range of 1 to 4 mol %. The Al2O3 content is preferably 3 mol % or less, and more preferably 2 mol % or more.

[0097] (MgO) MgO is an essential component for improving the melting property of glass. In order to fully obtain this effect, the content of MgO in this glass plate 1 is 8 mol% or more. Furthermore, if the content of MgO is less than 8 mol%, the surface compressive stress after chemical strengthening tends to decrease and the depth of the stress layer tends to become shallow. On the other hand, if the content is increased beyond an appropriate amount, the strengthening performance obtained by chemical strengthening decreases, and in particular, the depth of the surface compressive stress layer rapidly becomes shallow. This adverse effect is least pronounced for MgO among the alkaline earth metal oxides, but in this glass plate 1, the content of MgO is 15 mol% or less. Furthermore, if the content of MgO is high, T2 and T4 increase and the clarity of the glass melt deteriorates, making it difficult to manufacture a high-quality glass plate.

[0098] Therefore, in the glass plate 1, the content of MgO is in the range of 8 to 15 mol %, and preferably 12 mol % or less.

[0099] (CaO) CaO has the effect of reducing viscosity at high temperatures, but if the content is too high beyond a moderate range, the glass sheet 1 becomes more susceptible to devitrification and inhibits the movement of sodium ions in the glass sheet 1. When CaO is not contained, the surface compressive stress after chemical strengthening tends to decrease. On the other hand, when CaO is contained in an amount exceeding 8 mol%, the surface compressive stress after chemical strengthening significantly decreases, the compressive stress layer depth becomes significantly shallower, and the glass sheet 1 becomes more susceptible to devitrification.

[0100] Therefore, the CaO content is suitably in the range of 1 to 8 mol %. The CaO content is preferably 7 mol % or less, and more preferably 3 mol % or more.

[0101] (SrO, BaO) SrO and BaO significantly reduce the viscosity of the glass plate 1, and even a small amount of SrO and BaO can reduce the liquidus temperature T L However, even when added in small amounts, SrO and BaO significantly hinder the movement of sodium ions in the glass plate 1, significantly reducing the surface compressive stress, and making the depth of the compressive stress layer considerably shallower.

[0102] Therefore, it is preferable that the glass plate 1 does not substantially contain SrO or BaO.

[0103] (RO) In this embodiment, RO represents the sum of MgO and CaO. If the content of RO is too low, the components that reduce the viscosity of the glass plate 1 are insufficient, making it difficult to melt the glass plate 1. On the other hand, if the content of RO is too high, the surface compressive stress is significantly reduced, the depth of the compressive stress layer becomes significantly shallow, and the liquidus temperature T L tends to rise sharply.

[0104] Therefore, the appropriate RO content is in the range of 12 to 17 mol %. The RO content is preferably 14 mol % or more and 16 mol % or less.

[0105] Furthermore, when the molar ratio CaO / RO of the CaO content to the RO content is in the range of 0.1 to 0.4, the liquidus temperature tends to be particularly low. Therefore, this molar ratio is appropriate to be 0.1 to 0.4. Furthermore, if this molar ratio is lowered, the depth of the surface compressive stress / compressive stress layer can be improved, but T2 and T4 become higher and far from the narrow SL, making it difficult to manufacture the glass article. Therefore, this molar ratio is preferably 0.2 or more and 0.3 or less.

[0106] (Na2O) Na2O is a component that increases the surface compressive stress and deepens the depth of the surface compressive stress layer by replacing sodium ions with potassium ions. However, if the content is increased beyond an appropriate amount, the stress relaxation during the chemical strengthening process exceeds the surface compressive stress caused by ion exchange in the chemical strengthening process, and as a result, the surface compressive stress tends to decrease.

[0107] In addition, while Na2O is a component for improving solubility and lowering T4 and T2, if the Na2O content is too high, the water resistance of the glass is significantly reduced. In the glass plate 1, if the Na2O content is 12 mol% or more, the effect of lowering T4 and T2 is sufficiently obtained, but if it exceeds 16 mol%, the reduction in surface compressive stress due to stress relaxation becomes significant.

[0108] Therefore, the Na2O content in the glass plate 1 of the present embodiment is suitably in the range of 12 to 16 mol %. The Na2O content is preferably 13 mol % or more, and more preferably 15 mol % or less.

[0109] (K2O) Like Na2O, K2O is a component that improves the solubility of glass. In addition, when the content of K2O is low, the ion exchange rate during chemical strengthening increases, and the depth of the surface compressive stress layer increases, while the liquidus temperature T L Therefore, it is preferable to contain K2O at a low content.

[0110] On the other hand, compared with Na2O, K2O has a smaller effect of lowering T4 and T2, but a large amount of K2O inhibits the clarification of the glass melt. Also, the higher the K2O content, the lower the surface compressive stress after chemical strengthening. Therefore, the appropriate K2O content is in the range of 0 to 1 mol%.

[0111] (LiO) Even a small amount of Li2O significantly reduces the depth of the compressive stress layer. In addition, when a glass article containing Li2O is chemically strengthened with a molten salt of potassium nitrate alone, the molten salt deteriorates at a significantly faster rate than a glass article not containing Li2O. Specifically, when chemical strengthening is repeatedly performed with the same molten salt, the surface compressive stress formed on the glass surface decreases with fewer times. Therefore, the glass plate 1 of this embodiment may contain 1 mol% or less of Li2O, but it is preferable that it does not substantially contain Li2O.

[0112] (B2O3) B2O3 is a component that reduces the viscosity of the glass plate 1 and improves its solubility. However, if the content of B2O3 is too high, the glass plate 1 is prone to phase separation, and the water resistance of the glass plate 1 is reduced. In addition, compounds formed by B2O3 and alkali metal oxides may volatilize and damage the refractories in the glass melting chamber. Furthermore, the inclusion of B2O3 reduces the depth of the compressive stress layer in chemical strengthening. Therefore, the content of B2O3 is appropriate to be 0.5 mol% or less. In the present invention, it is more preferable that the glass plate 1 does not substantially contain B2O3.

[0113] (Fe2O3) Usually, Fe is 2+ or Fe 3+ It exists in glass as a colorant. 3+ is a component that enhances the ultraviolet absorbing performance of glass, and Fe 2+ is a component that enhances heat ray absorption performance. When the glass plate 1 is used as a cover glass for a display, it is required that the coloring is not noticeable, so the Fe content is preferably low. However, Fe is often inevitably mixed in as an industrial raw material. Therefore, the content of iron oxide converted to Fe2O3 is preferably 0.15% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.02% by mass or less, assuming that the entire glass plate 1 is 100% by mass. In particular, in the above-mentioned high-transmittance float glass, the Fe content is low, so that a high transmittance can be achieved. For example, when the thickness is 0.55 mm, the transmittance of light with a wavelength of 550 nm can be 91% or more and 100% or less.

[0114] (TiO2) TiO2 is a component that reduces the viscosity of the glass plate 1 and at the same time increases the surface compressive stress due to chemical strengthening, but it may impart a yellow color to the glass plate 1. Therefore, a TiO2 content of 0 to 0.2 mass % is appropriate. In addition, TiO2 is inevitably mixed in with commonly used industrial raw materials, and may be contained in the glass plate 1 at about 0.05 mass %. This level of content does not impart color to the glass, and therefore may be included in the glass plate 1 of the present embodiment.

[0115] (ZrO2) ZrO2 may be mixed into the glass sheet 1 from the firebricks that make up the glass melting furnace, particularly when manufacturing glass sheets by the float process, and it is known that the ZrO2 content is about 0.01% by mass. On the other hand, ZrO2 is a component that improves the water resistance of glass and also increases the surface compressive stress due to chemical strengthening. However, a high ZrO2 content increases the working temperature T4 and the liquidus temperature T L In the manufacture of glass sheets by the float method, the precipitated crystals containing Zr tend to remain as foreign matter in the manufactured glass. Therefore, the appropriate ZrO2 content is 0 to 0.1 mass%.

[0116] (SO3) In the float process, sulfates such as Glauber's salt (Na2SO4) are commonly used as fining agents. Sulfates decompose in molten glass to generate gas components, which promote degassing of the glass melt, but some of the gas components remain dissolved as SO3 in the glass plate 1. In the glass plate 1 of the present invention, the amount of SO3 is preferably 0 to 0.3 mass %.

[0117] (CeO2) CeO2 is used as a fining agent. CeO2 generates O2 gas in the molten glass, so CeO2 contributes to defoaming. On the other hand, if there is too much CeO2, the glass will be colored yellow. Therefore, the content of CeO2 is preferably 0 to 0.5 mass%, more preferably 0 to 0.3 mass%, and even more preferably 0 to 0.1 mass%.

[0118] (SnO2) It is known that in a glass sheet formed by a float method, tin diffuses from the tin bath to the surface that has been in contact with the tin bath during forming, and the tin exists as SnO2. In addition, SnO2 mixed in the glass raw material contributes to defoaming. In the glass sheet 1 of the present invention, SnO2 is preferably 0 to 0.3 mass%.

[0119] (Other Ingredients) The glass plate 1 according to the present embodiment is preferably substantially composed of the components listed above. However, the glass plate 1 according to the present embodiment may contain components other than the components listed above, preferably in such a range that the content of each component is less than 0.1 mass %.

[0120] Examples of components that may be included include As2O5, Sb2O5, Cl, and F, which are added for the purpose of defoaming molten glass other than the above-mentioned SO3 and SnO2. However, it is preferable not to add As2O5, Sb2O5, Cl, and F because of their large adverse effects on the environment. Other examples that may be included include ZnO, P2O5, GeO2, Ga2O3, Y2O3, and La2O3. Components other than those mentioned above that are derived from industrially used raw materials are allowed as long as they do not exceed 0.1 mass%. These components are added appropriately as necessary or are inevitably mixed in, so the glass plate 1 of this embodiment may not substantially contain these components.

[0121] (Density (specific gravity): d) From the above composition, in this embodiment, the density of the glass plate 1 is set to 2.53 g cm -3 Below that, 2.51 g cm -3 or less, in some cases 2.50 g cm -3 It can be reduced to the following:

[0122] In processes such as the float process, if there is a large difference in density between glass types, the molten glass with a higher density may remain at the bottom of the furnace when switching between glass types, which can cause problems when switching between types. The density of soda-lime glass currently mass-produced by the float process is approximately 2.50 g cm -3 Therefore, in consideration of mass production by the float method, the density of the glass plate 1 should be close to the above value, specifically, 2.45 to 2.55 g cm -3 , especially 2.47 to 2.53 g cm -3 is preferable, and 2.47 to 2.50 g cm -3 is more preferred.

[0123] (Elastic modulus: E) Chemical strengthening involving ion exchange may cause warping of the glass substrate. In order to suppress this warping, it is preferable that the elastic modulus of the glass plate 1 is high. According to the present invention, the elastic modulus (Young's modulus: E) of the glass plate 1 can be increased to 70 GPa or more, and even 72 GPa or more.

[0124] (Thermal expansion coefficient) In particular, the above-mentioned high-transmittance float glass has a thermal expansion coefficient of 50×10 between 50° C. and 350° C. -7 ~100×10 -7 / K% or less can be achieved.

[0125] <2-2-5. Orientation of glass plate> In a glass sheet manufactured by the float process, the surface that was in contact with the molten metal is referred to as the bottom surface, and the opposite surface is referred to as the top surface. The bottom surface and the top surface may be unpolished. Since the bottom surface was in contact with the molten metal, if the molten metal is tin, the concentration of tin oxide contained in the bottom surface will be greater than the concentration of tin oxide contained in the top surface.

[0126] In this way, the bottom surface has a high tin oxide concentration, which has the effect of suppressing the elution of alkaline components contained in the glass plate. When it is desired to suppress the deterioration of durability due to alkaline elution, the above-mentioned first functional layer 2 can be laminated on the bottom surface. On the other hand, the top surface has a low tin oxide concentration, so the concentration of SiOH groups on the surface is relatively high. Therefore, when it is desired to increase adhesion by utilizing the chemical bond between the OH groups of the first functional layer 2 and the surface SiOH groups, the first functional layer 2 can be laminated on the top surface. In addition, when it is desired to avoid the influence of trace metals (tin), the bottom surface can be polished with an abrasive such as cerium oxide, and the first functional layer 2 can be laminated on the bottom surface, the top surface, or both the bottom surface and the top surface. Note that the above points are the same not only for the first functional layer 2 but also for other functional layers described in this specification.

[0127] <2-2-6. Thickness of glass plate> The thickness of the glass plate 1 is not particularly limited, but is preferably 0.2 mm to 10 mm, and more preferably 0.5 mm to 4 mm. If the thickness of the glass plate 1 is less than 0.2 mm, the rigidity may be reduced, whereas if the thickness of the glass plate 1 is more than 10 mm, the weight may be heavy. As described above, even if the substrate 1 is made of a resin material, the substrate 1 can have the same thickness as the glass plate.

[0128] <3. 1st functional layer> The first functional layer 2 can be composed of films having various functions. For example, a heat-shielding film (heat-reflecting film) or an anti-fogging layer (or an anti-fogging sheet) can be used. The heat-shielding film is a known film configured to reflect or absorb infrared rays in order to suppress the temperature rise of the imaging device. Such a film can be attached to the first main surface 11 of the substrate 1 with an adhesive, or a film having a heat-shielding function can be laminated on the first main surface 11 by coating. In addition, another example of the first functional layer 2. The anti-fogging layer will be described in detail below.

[0129] <3-1. Anti-fogging layer> The anti-fogging layer is not particularly limited as long as it exerts an anti-fogging effect on the substrate 1, and a known anti-fogging layer can be used. In general, anti-fogging layers are classified into hydrophilic types that form a water film on the surface from water generated from water vapor, water-absorption types that absorb water vapor, water-repellent and water-absorption types that prevent water droplets from condensing on the surface, and water-repellent types that repel water droplets generated from water vapor, and any type of anti-fogging layer can be applied. As an example, an example of a water-repellent and water-absorption type anti-fogging layer will be described below. [Organic-inorganic composite anti-fog layer] The organic-inorganic composite anti-fogging layer is a single layer film or a laminated multi-layer film formed on the surface of any one of the functional layers. The organic-inorganic composite anti-fogging layer contains at least a water-absorbing resin, a water-repellent group, and a metal oxide component. The anti-fogging layer may further contain other functional components as necessary. The water-absorbing resin may be of any type as long as it is a resin that can absorb and retain water. The water-repellent group can be supplied to the anti-fogging layer from a metal compound having a water-repellent group (a water-repellent group-containing metal compound). The metal oxide component can be supplied to the anti-fogging layer from a water-repellent group-containing metal compound or other metal compounds, metal oxide fine particles, etc. Each component will be described below.

[0130] (Water absorbent resin) The water-absorbent resin is not particularly limited, and examples thereof include polyethylene glycol, polyether resin, polyurethane resin, starch resin, cellulose resin, acrylic resin, epoxy resin, polyester polyol, hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl acetal resin, polyvinyl acetate, etc. Among these, preferred are hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl acetal resin, polyvinyl acetate, epoxy resin, and polyurethane resin, more preferred are polyvinyl acetal resin, epoxy resin, and polyurethane resin, and particularly preferred is polyvinyl acetal resin.

[0131] Polyvinyl acetal resin can be obtained by acetalizing polyvinyl alcohol by condensation reaction with aldehyde. Acetalization of polyvinyl alcohol may be carried out by a known method such as a precipitation method using an aqueous medium in the presence of an acid catalyst, or a dissolution method using a solvent such as alcohol. Acetalization can also be carried out in parallel with saponification of polyvinyl acetate. The degree of acetalization is preferably 2 to 40 mol%, more preferably 3 to 30 mol%, particularly preferably 5 to 20 mol%, and in some cases 5 to 15 mol%. The degree of acetalization can be, for example, 13 The degree of acetalization can be measured based on C nuclear magnetic resonance spectroscopy. A polyvinyl acetal resin having an acetalization degree within the above range is suitable for forming an organic-inorganic composite anti-fogging layer having good water absorbency and water resistance.

[0132] The average polymerization degree of polyvinyl alcohol is preferably 200 to 4500, more preferably 500 to 4500. A high average polymerization degree is advantageous for the formation of an organic-inorganic composite anti-fogging layer having good water absorption and water resistance, but if the average polymerization degree is too high, the viscosity of the solution becomes too high, which may cause problems in the formation of the film. The saponification degree of polyvinyl alcohol is preferably 75 to 99.8 mol%.

[0133] Examples of the aldehyde to be condensed with polyvinyl alcohol include aliphatic aldehydes such as formaldehyde, acetaldehyde, butylaldehyde, hexylcarbaldehyde, octylcarbaldehyde, and decylcarbaldehyde. Examples of the aldehyde to be condensed with polyvinyl alcohol include benzaldehyde; 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, and other alkyl group-substituted benzaldehydes; chlorobenzaldehyde and other halogen atom-substituted benzaldehydes; substituted benzaldehydes in which hydrogen atoms are substituted with functional groups other than alkyl groups such as hydroxyl groups, alkoxy groups, amino groups, and cyano groups; and aromatic aldehydes such as condensed aromatic ring aldehydes such as naphthaldehyde and anthraldehyde. Aromatic aldehydes that are highly hydrophobic are advantageous in forming an organic-inorganic composite anti-fogging layer that has a low degree of acetalization and excellent water resistance. The use of an aromatic aldehyde is advantageous in that a film having high water absorption can be formed while leaving many hydroxyl groups. The polyvinyl acetal resin preferably contains an acetal structure derived from an aromatic aldehyde, particularly benzaldehyde.

[0134] Examples of epoxy resins include glycidyl ether epoxy resins, glycidyl ester epoxy resins, glycidyl amine epoxy resins, cyclic aliphatic epoxy resins, etc. Among these, cyclic aliphatic epoxy resins are preferred.

[0135] The polyurethane resin may be a polyurethane resin composed of a polyisocyanate and a polyol. As the polyol, an acrylic polyol and a polyoxyalkylene polyol are preferable.

[0136] The cellulose-based resin may be TAC (triacetyl cellulose) whose surface has been modified. Examples of the modification method include a physical modification method and a chemical modification method. Examples of the physical modification method include an active ray irradiation method, a plasma treatment method, and a corona discharge treatment method. Examples of the chemical modification method include converting an acyl group in the TAC structure to a hydroxyl group to make the surface hydrophilic (see, for example, JP 2017-57370 and JP 2017-57242). Specifically, the acyl group in the TAC structure can be converted to a hydroxyl group by swelling the TAC with alcohol, saponifying it with KOH water, heat treating it, and neutralizing and washing it. By such a saponification treatment, it is possible to obtain a surface-modified TAC having a thickness of 10 to 200 μm and a modified layer of TAC having a thickness of 1 to 6 μm. The modified layer of TAC functions as an anti-fogging layer. The anti-reflection layer of the present invention may be formed on the modified layer of TAC (anti-fogging layer). The thickness of the TAC may be evaluated based on the Japanese Industrial Standards (JIS.K7130:1999. Plastics - Films and Sheets - Thickness Measurement Method). When the modified layer is a saponified layer obtained by saponification, the thickness of the saponified layer may be determined by the following method. A sample taken from the anti-fog film is immersed in dichloromethane for 24 hours. The sample that remains undissolved after immersion is dried, and the thickness of the dried sample is measured three times. The average of the three measured values ​​is taken as the thickness of the saponified layer (see, for example,

[0039] of JP 2017-57370 A).

[0137] The organic-inorganic composite anti-fogging layer contains a water-absorbing resin as a main component. In the present invention, the "main component" means the component having the highest content by mass. The content of the water-absorbing resin based on the weight of the organic-inorganic composite anti-fogging layer is preferably 50% by mass or more, more preferably 60% by mass or more, particularly preferably 65% ​​by mass or more, and is 95% by mass or less, more preferably 90% by mass or less, from the viewpoints of film hardness, water absorbency, and anti-fogging properties.

[0138] (Water-repellent base) In order to fully obtain the above-mentioned effects of the water-repellent group, it is preferable to use a water-repellent group having high water repellency. The preferred water-repellent group is at least one selected from (1) linear or cyclic alkyl groups having 3 to 30 carbon atoms, and (2) linear or cyclic alkyl groups having 1 to 30 carbon atoms in which at least a portion of the hydrogen atoms has been substituted with fluorine atoms (hereinafter sometimes referred to as "fluorine-substituted alkyl groups").

[0139] Regarding (1) and (2), the chain or cyclic alkyl group is preferably a chain alkyl group. The chain alkyl group may be a branched alkyl group, but is preferably a linear alkyl group. An alkyl group having more than 30 carbon atoms may cause the antifogging layer to become cloudy. From the viewpoint of the balance between the antifogging property, strength, and appearance of the film, the number of carbon atoms of the alkyl group is preferably 20 or less, more preferably 6 to 14. Particularly preferred alkyl groups are linear alkyl groups having 6 to 14 carbon atoms, particularly 6 to 12 carbon atoms, such as n-hexyl group (6 carbon atoms), n-decyl group (10 carbon atoms), and n-dodecyl group (12 carbon atoms). Regarding (2), the fluorine-substituted alkyl group may be a group in which only a part of the hydrogen atoms of a chain or cyclic alkyl group are substituted with fluorine atoms, or a group in which all of the hydrogen atoms of a chain or cyclic alkyl group are substituted with fluorine atoms, such as a linear perfluoroalkyl group. Since the fluorine-substituted alkyl group has high water repellency, a sufficient effect can be obtained by adding a small amount of it. However, if the content of the fluorine-substituted alkyl group is too high, it may separate from other components in the coating liquid for forming the film.

[0140] (Hydrolyzable metal compounds having water-repellent groups) In order to incorporate water-repellent groups into the anti-fogging layer, a metal compound having a water-repellent group (water-repellent group-containing metal compound), particularly a metal compound having a water-repellent group and a hydrolyzable functional group or a halogen atom (water-repellent group-containing hydrolyzable metal compound) or its hydrolyzate may be added to the coating liquid for forming the film. In other words, the water-repellent group may be derived from a water-repellent group-containing hydrolyzable metal compound. As the water-repellent group-containing hydrolyzable metal compound, a water-repellent group-containing hydrolyzable silicon compound represented by the following formula (I) is suitable. R m SiY 4-m (I) Here, R is a water-repellent group, that is, a linear or cyclic alkyl group having 1 to 30 carbon atoms in which at least a part of hydrogen atoms may be substituted with fluorine atoms, Y is a hydrolyzable functional group or a halogen atom, and m is an integer of 1 to 3. The hydrolyzable functional group is, for example, at least one selected from an alkoxyl group, an acetoxy group, an alkenyloxy group, and an amino group, and is preferably an alkoxy group, particularly an alkoxy group having 1 to 4 carbon atoms. The alkenyloxy group is, for example, an isopropenoxy group. The halogen atom is preferably chlorine. The functional groups exemplified here can also be used as the "hydrolyzable functional group" described below. m is preferably 1 to 2.

[0141] Upon completion of hydrolysis and polycondensation, the compound represented by formula (I) provides a component represented by the following formula (II): R m SiO (4-m) / 2 (II) where R and m are as defined above. After hydrolysis and polycondensation, the compound represented by formula (II) actually forms a network structure in the anti-fog layer in which silicon atoms are bonded to each other via oxygen atoms.

[0142] In this way, the compound represented by formula (I) is hydrolyzed or partially hydrolyzed, and further at least partially polycondensed to form a network structure of siloxane bonds (Si-O-Si) in which silicon atoms and oxygen atoms are alternately connected and spread three-dimensionally. The silicon atoms contained in this network structure are connected to water-repellent groups R. In other words, the water-repellent groups R are fixed to the network structure of siloxane bonds via bonds R-Si. This structure is advantageous in terms of uniformly dispersing the water-repellent groups R in the film. The network structure may contain a silica component provided by a silicon compound (e.g., tetraalkoxysilane, silane coupling agent) other than the water-repellent group-containing hydrolyzable silicon compound represented by formula (I). When a silicon compound (water-repellent group-free hydrolyzable silicon compound) having no water-repellent groups and a hydrolyzable functional group or halogen atom and a halogen atom is blended with the water-repellent group-containing hydrolyzable silicon compound in the coating liquid for forming the anti-fogging layer, a network structure of siloxane bonds including silicon atoms bonded to water-repellent groups and silicon atoms not bonded to water-repellent groups can be formed. With such a structure, it becomes easy to adjust the content of the water-repellent group and the content of the metal oxide component in the anti-fogging layer independently of each other.

[0143] The water-repellent group has the effect of improving the permeability of water vapor on the surface of the anti-fogging layer containing the water-absorbing resin, thereby improving the anti-fogging performance. Since the two functions of water absorption and water repellency are mutually exclusive, water-absorbing materials and water-repellent materials have been conventionally provided in separate layers, but the water-repellent group eliminates uneven distribution of water near the surface of the anti-fogging layer, prolonging the time until condensation occurs, thereby improving the anti-fogging properties of the anti-fogging layer having a single layer structure. The effects of this will be explained below.

[0144] Water vapor that penetrates into an anti-fogging layer containing a water-absorbing resin forms hydrogen bonds with hydroxyl groups of the water-absorbing resin and is held in the form of bound water. As the amount of water increases, the water vapor changes from bound water to semi-bound water, and finally to free water held in the voids in the anti-fogging layer. In the anti-fogging layer, the water-repellent groups prevent the formation of hydrogen bonds and facilitate the dissociation of the hydrogen bonds that have been formed. If the content of the water-absorbing resin is the same, there is no difference in the number of hydroxyl groups capable of hydrogen bonding in the film, but the water-repellent groups slow down the rate of formation of hydrogen bonds. Therefore, when the content of water-absorbing resin is the same, the water-repellent groups prevent the formation of hydrogen bonds in the film, and the number of hydrogen-bondable hydroxyl groups in the film is the same. In the anti-fogging layer having the above structure, moisture is ultimately retained in the film in any of the above forms, but before it is retained, it can diffuse as water vapor to the bottom of the film. In addition, water that is once retained is relatively easily dissociated and easily moves to the bottom of the film in the form of water vapor. As a result, the distribution of the amount of moisture retained in the thickness direction of the film is relatively uniform from the vicinity of the surface to the bottom of the film. In other words, the entire thickness direction of the anti-fogging layer can be effectively utilized to absorb water supplied to the film surface, so that water droplets are less likely to condense on the surface, and anti-fogging properties are improved. Furthermore, since water droplets are less likely to condense on the surface, the anti-fogging layer that has absorbed moisture has the characteristic of being less likely to freeze even at low temperatures.

[0145] On the other hand, in the anti-fogging layer that does not contain water repellent groups, the water vapor that penetrates into the film is very easily retained in the form of bound water, semi-bound water or free water. Therefore, the water vapor that penetrates tends to be retained near the surface of the film. As a result, the moisture in the film is extremely high near the surface and decreases rapidly as it progresses to the bottom of the film. In other words, although the bottom of the film can still absorb water, the moisture near the surface of the film is saturated with moisture and condenses as water droplets, resulting in limited anti-fogging properties.

[0146] When a water-repellent group is introduced into the anti-fogging layer using a hydrolyzable silicon compound containing a water-repellent group (see formula (I)), a strong network structure of siloxane bonds (Si-O-Si) is formed. The formation of this network structure is advantageous not only in terms of abrasion resistance but also in terms of improving hardness, water resistance, etc.

[0147] The water-repellent group is preferably added to such an extent that the contact angle of water on the surface of the anti-fogging layer is 70 degrees or more, preferably 80 degrees or more, more preferably 90 degrees or more. The water contact angle is measured by dropping 4 mg of water droplets on the surface of the film. In particular, when a methyl group or an ethyl group, which has a relatively weak water repellency, is used as the water-repellent group, it is preferable to incorporate the water-repellent group in the anti-fogging layer in an amount that makes the water contact angle in the above range. The upper limit of this water droplet contact angle is not particularly limited, but it is, for example, 150 degrees or less, for example, 120 degrees or less, or even 100 degrees or less. It is preferable that the water-repellent group is uniformly contained in the anti-fogging layer so that the contact angle of the water droplet is in the above range in all areas of the surface of the anti-fogging layer.

[0148] The surface of the anti-fogging layer can also be made water-repellent, which can prevent alkaline components from penetrating into the anti-fogging layer and protect the surface of the glass plate 1 from alkaline components.

[0149] The anti-fogging layer preferably contains water-repellent groups in an amount within the range of 0.05 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and 10 parts by mass or less, preferably 5 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin.

[0150] (Inorganic oxides) The inorganic oxide is, for example, an oxide of at least one element selected from Si, Ti, Zr, Ta, Nb, Nd, La, Ce and Sn, and contains at least an oxide of Si (silica). The organic-inorganic composite anti-fogging layer preferably contains 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, even more preferably 0.2 parts by weight or more, particularly preferably 1 part by weight or more, most preferably 5 parts by weight or more, in some cases 10 parts by weight or more, if necessary 20 parts by weight or more, and preferably 50 parts by weight or less, more preferably 45 parts by weight or less, even more preferably 40 parts by weight or less, particularly preferably 35 parts by weight or less, most preferably 33 parts by weight or less, in some cases 30 parts by weight or less, relative to 100 parts by weight of the water-absorbing resin. The inorganic oxide is a component necessary for ensuring the strength, particularly the abrasion resistance, of the organic-inorganic composite anti-fogging layer, but if the content of the inorganic oxide is high, the anti-fogging property of the organic-inorganic composite anti-fogging layer decreases.

[0151] (Inorganic oxide fine particles) The organic-inorganic composite anti-fogging layer may further contain inorganic oxide fine particles as at least a part of the inorganic oxide. The inorganic oxide constituting the inorganic oxide fine particles is, for example, an oxide of at least one element selected from Si, Ti, Zr, Ta, Nb, Nd, La, Ce and Sn, and is preferably silica fine particles. The silica fine particles can be introduced into the organic-inorganic composite anti-fogging layer by, for example, adding colloidal silica. The inorganic oxide fine particles are excellent in the function of transmitting the stress applied to the organic-inorganic composite anti-fogging layer to the article supporting the organic-inorganic composite anti-fogging layer, and also have high hardness. Therefore, the addition of inorganic oxide fine particles is advantageous from the viewpoint of improving the abrasion resistance of the organic-inorganic composite anti-fogging layer. In addition, when inorganic oxide fine particles are added to the organic-inorganic composite anti-fogging layer, fine voids are formed at the site where the fine particles are in contact or in close proximity, and water vapor is easily taken into the film through these voids. For this reason, the addition of inorganic oxide fine particles may be advantageous in improving the anti-fogging properties. The inorganic oxide fine particles can be provided to the organic-inorganic composite anti-fogging layer by adding preformed inorganic oxide fine particles to a coating liquid for forming the organic-inorganic composite anti-fogging layer.

[0152] If the average particle size of the inorganic oxide fine particles is too large, the organic-inorganic composite anti-fogging layer may become cloudy, and if it is too small, it may become difficult to disperse the inorganic oxide fine particles uniformly due to aggregation. From this viewpoint, the average particle size of the inorganic oxide fine particles is preferably 1 to 20 nm, more preferably 5 to 20 nm. Here, the average particle size of the inorganic oxide fine particles is described in the state of primary particles. The average particle size of the inorganic oxide fine particles is determined by measuring the particle sizes of 50 particles arbitrarily selected by observation using a scanning electron microscope and adopting the average value. If the content of the inorganic oxide fine particles is high, the water absorption amount of the organic-inorganic composite anti-fogging layer as a whole may decrease, and the organic-inorganic composite anti-fogging layer may become cloudy. The inorganic oxide fine particles are preferably added in an amount of 0 to 50 parts by weight, more preferably 2 to 30 parts by weight, further preferably 5 to 25 parts by weight, and particularly preferably 10 to 20 parts by weight, relative to 100 parts by weight of the water-absorbing resin.

[0153] (Hydrolyzable metal compounds without water-repellent groups) The anti-fogging layer may contain a metal oxide component derived from a hydrolyzable metal compound that does not have a water-repellent group (hydrolyzable compound that does not contain a water-repellent group). A preferred hydrolyzable metal compound that does not contain a water-repellent group is a hydrolyzable silicon compound that does not have a water-repellent group. The hydrolyzable silicon compound that does not have a water-repellent group is, for example, at least one silicon compound (not having a water-repellent group) selected from silicon alkoxide, chlorosilane, acetoxysilane, alkenyloxysilane, and aminosilane, and is preferably a silicon alkoxide that does not have a water-repellent group. An example of the alkenyloxysilane is isopropenoxysilane.

[0154] The hydrolyzable silicon compound having no water repellent group may be a compound represented by the following formula (III). SiY4(III) As described above, Y is a hydrolyzable functional group, and is preferably at least one selected from an alkoxyl group, an acetoxy group, an alkenyloxy group, an amino group, and a halogen atom.

[0155] The hydrolyzable metal compound not containing a water-repellent group is hydrolyzed or partially hydrolyzed, and further, at least a part of the compound is polycondensed to provide a metal oxide component in which a metal atom is bonded to an oxygen atom. This component firmly bonds the metal oxide fine particles to the water-absorbent resin, and can contribute to improving the abrasion resistance, hardness, water resistance, etc. of the anti-fogging layer. The metal oxide component derived from the hydrolyzable metal compound not containing a water-repellent group is preferably in the range of 0 to 40 parts by mass, preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, particularly preferably 3 to 10 parts by mass, and in some cases 4 to 12 parts by mass, relative to 100 parts by mass of the water-absorbent resin.

[0156] A preferred example of a hydrolyzable silicon compound having no water-repellent group is a tetraalkoxysilane, more specifically, a tetraalkoxysilane having an alkoxy group having a carbon number of 1 to 4. The tetraalkoxysilane is, for example, at least one selected from tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetraisobutoxysilane, tetra-sec-butoxysilane, and tetra-tert-butoxysilane.

[0157] If the content of the metal oxide (silica) component derived from tetraalkoxysilane is too high, the antifogging properties of the antifogging layer may decrease. One of the reasons is that the flexibility of the antifogging layer decreases, limiting the swelling and shrinkage of the film accompanying the absorption and release of moisture. The metal oxide component derived from tetraalkoxysilane is added in the range of 0 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 3 to 10 parts by mass, relative to 100 parts by mass of the water-absorbing resin.

[0158] Another preferred example of the hydrolyzable silicon compound without a water-repellent group is a silane coupling agent. The silane coupling agent is a silicon compound having reactive functional groups different from each other. The reactive functional group is preferably a part of a hydrolyzable functional group. The silane coupling agent is, for example, a silicon compound having an epoxy group and / or an amino group and a hydrolyzable functional group. Preferred silane coupling agents include glycidyloxyalkyltrialkoxysilane and aminoalkyltrialkoxysilane. In these silane coupling agents, the number of carbon atoms of the alkylene group directly bonded to the silicon atom is preferably 1 to 3. Since the glycidyloxyalkyl group and the aminoalkyl group contain a functional group (epoxy group, amino group) that shows hydrophilicity, they are not water-repellent as a whole, although they contain an alkylene group.

[0159] The silane coupling agent strongly bonds the water-absorbing resin, which is an organic component, with the metal oxide fine particles, which are inorganic components, and can contribute to improving the abrasion resistance, hardness, water resistance, etc. of the anti-fogging layer. However, if the content of the metal oxide (silica) component derived from the silane coupling agent is excessive, the anti-fogging properties of the anti-fogging layer are reduced, and in some cases the anti-fogging layer becomes cloudy. The metal oxide component derived from the silane coupling agent is added in a range of 0 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 2 parts by mass, relative to 100 parts by mass of the water-absorbing resin.

[0160] (Crosslinked structure) The anti-fogging layer may contain a crosslinked structure derived from a crosslinking agent, preferably at least one crosslinking agent selected from an organic boron compound, an organic titanium compound, and an organic zirconium compound. The introduction of the crosslinked structure improves the abrasion resistance, scratch resistance, and water resistance of the anti-fogging layer. From another perspective, the introduction of the crosslinked structure makes it easy to improve the durability of the anti-fogging layer without reducing its anti-fogging performance.

[0161] When a crosslinked structure derived from a crosslinking agent is introduced into an anti-fogging layer whose metal oxide component is a silica component, the anti-fogging layer may contain, as a metal atom, silicon as well as a metal atom other than silicon, preferably boron, titanium or zirconium.

[0162] The crosslinking agent is not particularly limited in type as long as it can crosslink the water-absorbent resin used. Here, only examples of organic titanium compounds are given. The organic titanium compound is, for example, at least one selected from titanium alkoxides, titanium chelate-based compounds, and titanium acylates. Examples of titanium alkoxides include titanium tetraisopropoxide, titanium tetra-n-butoxide, and titanium tetraoctoxide. Examples of titanium chelate-based compounds include titanium acetylacetonate, titanium ethyl acetoacetate, titanium octylene glycol, titanium triethanolamine, and titanium lactate. Titanium lactate may be an ammonium salt (ammonium titanium lactate). Titanium acylate is, for example, titanium stearate. Preferred organotitanium compounds are titanium chelate-based compounds, especially titanium lactate.

[0163] When the water-absorbing resin is a polyvinyl acetal, the preferred crosslinking agent is an organotitanium compound, especially titanium lactate.

[0164] (Other optional ingredients) The anti-fogging layer may contain other additives. Examples of the additives include glycols such as glycerin and ethylene glycol, which have the function of improving the anti-fogging properties. The additives may be surfactants, leveling agents, ultraviolet absorbers, colorants, defoamers, preservatives, etc.

[0165] (base layer) The anti-fogging layer can be laminated directly on each of the functional layers 3 and 4, or a base layer can be formed on each of the functional layers 3 and 4, and the anti-fogging layer can be laminated on the base layer. By laminating the anti-fogging layer on each of the functional layers 3 and 4 through the base layer in this manner, the anti-fogging layer can be made less likely to peel off. For example, a silane coupling agent or the like can be used as the base layer.

[0166] Thickness The thickness of the organic-inorganic composite anti-fogging layer may be appropriately adjusted depending on the required anti-fogging properties and other factors. The thickness of the organic-inorganic composite anti-fogging layer is preferably 1 to 20 μm, more preferably 2 to 15 μm, even more preferably 2 to 12 μm, and particularly preferably 3 to 10 μm. If the thickness of the anti-fogging layer is 1 μm or more, a sufficient anti-fogging effect can be obtained. On the other hand, if the anti-fogging layer is too thick, the reflected image may be distorted due to unevenness in the film thickness. In addition, since the anti-fogging layer is formed from a resin material as described above and has birefringence, if it is too thick, the image may become blurred.

[0167] <3-2. Method for forming anti-fogging layer> The method for forming the anti-fogging layer having the above-mentioned composition is not particularly limited, but for example, the layer can be formed by the following method.

[0168] First, the coating liquid for the organic-inorganic composite anti-fogging layer (anti-fogging layer solution) is prepared. Next, the coating liquid is applied to the substrate 1 by a coater, and then dried in a first heating furnace.

[0169] When applying the coating liquid, it is preferable to maintain the relative humidity of the atmosphere at less than 60%, and more preferably at 40% or less. Maintaining a low relative humidity can prevent the organic-inorganic composite anti-fogging layer from absorbing excessive moisture from the atmosphere. If a large amount of moisture is absorbed from the atmosphere, the water that remains in the matrix of the organic-inorganic composite anti-fogging layer may reduce the strength of the film.

[0170] In the first heating furnace, heating is preferably performed at 200°C or less, for example, 50 to 150°C. The heating time is preferably 1 to 20 minutes, and more preferably 2 to 10 minutes. This heating can be performed multiple times. For example, heating can be performed for 3 to 5 minutes two or more times. In this way, the coating liquid is baked, and a crosslinked structure of the water-absorbent resin and Si is formed. However, this is not a strong crosslinked structure formed by completely baking the coating liquid, but a provisional anti-fogging layer.

[0171] Next, the substrate dried as described above is immersed in a water tank. This causes the anti-fogging layer to swell on the substrate 1, and some of the crosslinking points are broken. In addition, impurities contained in the water absorbent resin, such as Na and Cl, are removed. Furthermore, uncrosslinked water absorbent resin composition is also removed. The water stored in the water tank can be, for example, 10 to 80°C, more preferably 20 to 60°C, and particularly preferably 25 to 50°C. The temperature of the water may be less than 10°C, but if it is lower than 10°C, the effect of removing the alkaline component may be reduced. On the other hand, if it is higher than 80°C, the amount of water vapor evaporated from the water tank may increase, and the load on the equipment and working environment may increase. From the above viewpoints, in order to reduce the load on the equipment and environment while maintaining a relatively high effect of removing the alkaline component, the water temperature is particularly preferably 25 to 50°C. In addition, the time for immersion in the water tank can be, for example, 1 to 30 minutes, more preferably 3 to 20 minutes, and particularly preferably 3 to 10 minutes. Even when the water temperature is low and the efficiency of removing the alkaline components is low as described above, the alkaline components can be sufficiently removed by extending the immersion time. However, since a long immersion time reduces production efficiency, it is particularly preferable to set the immersion time to 3 to 10 minutes. For example, the immersion can be performed in water at 25 to 50°C for about 3 to 10 minutes. This water treatment can also be performed multiple times. In this way, by performing the water treatment multiple times, the effects described below can be obtained even in a small water tank without enlarging the tank size.

[0172] Next, the substrate 1 is heated in a second heating furnace. In this second heating furnace, the swollen anti-fogging layer is baked, and the cross-linked structure of the water-absorbent resin and Si remaining in the anti-fogging layer is strengthened. The heating temperature in this heating furnace is preferably 200°C or less, for example, 50 to 150°C, as in the above-mentioned first heating furnace. The heating time is longer than that in the first heating furnace, for example, preferably 3 to 60 minutes, and more preferably 5 to 30 minutes. In this way, the anti-fogging layer is sufficiently baked, and the anti-fogging layer is completed.

[0173] <3-3. Anti-fogging layer with hydrophilic layer> The anti-fogging layer described above mainly has a moisture absorbing function, and a hydrophilic layer can be further formed on this anti-fogging layer (moisture absorbing layer), as will be described in detail below.

[0174] This hydrophilic layer can have various configurations, but for example, it can contain polyether-modified dimethylsiloxane represented by the following formula (A). [ka] However, m, n, x, and y are independently integers of 1 or more; R 1 is a hydrogen atom or a methyl group, R 2 is an alkyl group having 1 to 3 carbon atoms.

[0175] Moreover, the above formula (A) can be further configured as follows. (1) The average molecular weight of the polyether-modified dimethylsiloxane can be set to 3,000 to 300,000. (2) m can be an integer of 2 or 3. In other words, the connection between the silicone main chain, its side chain, and the polyether side chain is an ethylene group or a propylene group. The vinyl-modified dimethylsiloxane can be obtained by addition reaction of dimethylpolysiloxane in which some of the methyl groups in the dimethylpolysiloxane main chain have been replaced with hydrogen atoms, with polyether having vinyl groups at the terminals. (3) The degree of polymerization n of the polyether side chain can be an integer of 3 to 600. In other words, the molecular weight of polyethylene glycol is about 200 to 20,000 (degree of polymerization is about 4 to 400). (4) The modification ratio, y / (x+y), can be 0.01 or more and less than 1. In other words, at least one out of 100 siloxane units can be modified, and all (except for both ends) can be modified.

[0176] The above-mentioned hydrophilic layer may be formed by any conventional method. For example, the polyether-modified dimethylsiloxane may be used as is or diluted with a solvent capable of dissolving it, soaked into cotton cloth, and rubbed onto the anti-fogging layer with the cotton cloth. Alternatively, the diluted solution may be applied onto the anti-fogging layer by spray coating, flow coating, or the like, and the solvent may be evaporated to dry.

[0177] By forming such a hydrophilic layer, the following effects can be obtained. For example, when the moisture absorption of the hygroscopic anti-fogging layer progresses and becomes saturated, water vapor adheres to the hydrophilic layer, but a water film is formed on the surface of the hydrophilic layer due to its hydrophilic function. Therefore, even though a water film is formed after the anti-fogging layer becomes saturated, the occurrence of fogging due to water droplets can be suppressed.

[0178] <3-4. Anti-fogging layer with hydrophilic properties> Next, the anti-fogging layer having a hydrophilic function will be described. The anti-fogging layer described in the above section 3-3 has a separate hydrophilic layer, but the anti-fogging layer in this section contains a hydrophilic function and is formed as a single layer.

[0179] In this anti-fogging layer, a hydrophilizing agent is dispersed inside the anti-fogging layer having the moisture absorbing function described above. This improves the hydrophilicity on the surface of the anti-fogging layer. That is, even if the water-absorbing resin described above is saturated with water, a water film can be formed on the surface of the anti-fogging layer to maintain the anti-fogging properties. In addition, when a hydrophilic layer is separately formed on the anti-fogging layer as described above, the apparent refractive index of the hydrophilic layer is higher than that of the anti-fogging layer, so that glare may occur. On the other hand, when a hydrophilizing agent is dispersed inside the anti-fogging layer, glare can be suppressed. Furthermore, when a hydrophilizing agent is dispersed in the anti-fogging layer, for example, even if the hydrophilizing agent on the surface is removed by wiping or the like, the hydrophilizing agent inside appears on the surface, so that the hydrophilic performance can be maintained. The hydrophilizing agent is not particularly limited, and for example, any of anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants can be used. As the anionic surfactant, for example, sodium dialkyl sulfosuccinate can be used.

[0180] The anti-fogging layer can contain a solvent with a high boiling point, for example, a solvent with a boiling point of 100°C or more and 300°C or less. This allows the solvent to be dispersed in the anti-fogging layer, even if the anti-fogging layer is baked at 100°C or more when it is formed. The hydrophilizing agent dissolves in the solvent, and the hydrophilizing agent can be dispersed in the anti-fogging layer. Meanwhile, resins containing organic materials generally have a heat resistance temperature of 300°C or less, since they turn yellow or are thermally decomposed. Therefore, when a solvent with a boiling point higher than 300°C is used, if the anti-fogging layer is baked at 300°C or less, there is a risk that too much solvent will remain in the anti-fogging layer. Therefore, the boiling point of the solvent used here is preferably 300°C or less. Such a solvent preferably has an alcohol group, which makes it easier to disperse the hydrophilizing agent in the solvent. Specifically, for example, propylene glycol, polyethylene glycol, triethylene glycol, or glycerin can be used.

[0181] The anti-fogging layer as described above can be formed, for example, as follows. First, the above-mentioned solvent and hydrophilizing agent are added to the coating liquid for the organic-inorganic composite anti-fogging layer to produce an anti-fogging layer solution. Then, this anti-fogging layer solution is applied to the substrate 1 by a method such as spin coating, roll coating, or spray coating. Next, the solution is dried by air cooling and then baked in a heating furnace. Then, the anti-fogging layer is completed by air cooling at room temperature. Since this anti-fogging layer contains a hydrophilizing agent inside, the anti-fogging layer can be formed by performing the coating step and the baking step once each. Therefore, the manufacturing time can be significantly reduced. The addition ratio of the high boiling point solvent in the coating liquid is preferably, for example, 0.1 to 40 mass%, and the addition ratio of the hydrophilizing agent is preferably, for example, 0.01 to 1.0 mass%.

[0182] <3-5. Anti-fogging layer mainly composed of inorganic compounds> <3-5-1. Composition of the anti-fogging layer> Next, an anti-fogging layer mainly composed of an inorganic compound will be described. This anti-fogging layer has an uneven surface, and under high humidity conditions, a water film is formed on the surface, thereby exerting anti-fogging performance. That is, it functions as a so-called hydrophilic anti-fogging layer. In addition, by forming such unevenness, the refractive index can be reduced in appearance, and surface reflection can be suppressed.

[0183] Such an anti-fogging layer can contain, for example, inorganic fine particles and inorganic binders. Furthermore, photocatalyst fine particles can also be contained. By containing photocatalyst fine particles, hydrocarbons and organic dirt accumulated on the surface of the anti-fogging layer are decomposed, and a water film is easily formed. For example, if hydrocarbons and organic dirt accumulate on the surface of the anti-fogging layer, the contact angle becomes high and optical distortion may occur when water droplets adhere to the surface. In contrast, if photocatalyst particles are added, the dirt on the surface is decomposed, and the optical distortion caused by the adhesion of water can be suppressed.

[0184] Examples of inorganic fine particles include SiO2, ZrO2, CeO2, ZnO, Al2O3, Nb2O5, It can be formed of Y2O3 and MgO. The particle diameter of the inorganic fine particles is, for example, preferably 1 to 500 nm, more preferably 5 to 200 nm, or 10 to 150 nm. If the particle diameter of the inorganic fine particles is large, the haze ratio increases, which is not preferable.

[0185] The inorganic binder may contain a metal oxide component derived from a hydrolyzable metal compound. A preferred hydrolyzable metal compound is a hydrolyzable silicon compound having no water-repellent group. The hydrolyzable silicon compound having no water-repellent group is, for example, at least one silicon compound (having no water-repellent group) selected from silicon alkoxide, chlorosilane, acetoxysilane, alkenyloxysilane, and aminosilane, and silicon alkoxide having no water-repellent group is preferred. An example of the alkenyloxysilane is isopropenoxysilane.

[0186] The hydrolyzable silicon compound having no water repellent group may be a compound represented by the following formula (III). SiY4(III) As described above, Y is a hydrolyzable functional group, and is preferably at least one selected from an alkoxyl group, an acetoxy group, an alkenyloxy group, an amino group, and a halogen atom.

[0187] The hydrolyzable metal compound not containing a water-repellent group is hydrolyzed or partially hydrolyzed, and at least a part of the compound is polycondensed to provide a metal oxide component in which a metal atom is bonded to an oxygen atom. This component firmly bonds the inorganic fine particles or the photocatalyst fine particles to the substrate or substrate film, and the inorganic fine particles and the photocatalyst fine particles to each other, and can contribute to improving the abrasion resistance, hardness, water resistance, etc. of the anti-fogging layer.

[0188] A preferred example of a hydrolyzable silicon compound having no water-repellent group is a tetraalkoxysilane, more specifically, a tetraalkoxysilane having an alkoxy group having a carbon number of 1 to 4. The tetraalkoxysilane is, for example, at least one selected from tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetraisobutoxysilane, tetra-sec-butoxysilane, and tetra-tert-butoxysilane.

[0189] Another preferred example of the hydrolyzable silicon compound without a water-repellent group is a silane coupling agent. The silane coupling agent is a silicon compound having reactive functional groups different from each other. The reactive functional group is preferably a part of a hydrolyzable functional group. The silane coupling agent is, for example, a silicon compound having an epoxy group and / or an amino group and a hydrolyzable functional group. Preferred silane coupling agents include glycidyloxyalkyltrialkoxysilane and aminoalkyltrialkoxysilane. In these silane coupling agents, the number of carbon atoms of the alkylene group directly bonded to the silicon atom is preferably 1 to 3. Since the glycidyloxyalkyl group and the aminoalkyl group contain a functional group (epoxy group, amino group) that shows hydrophilicity, they are not water-repellent as a whole, although they contain an alkylene group.

[0190] The photocatalyst fine particles can be formed of, for example, an oxide or oxynitride mainly composed of any one of titanium, tungsten, and iron. The particle diameter of the photocatalyst fine particles is, for example, preferably 1 to 50 nm, more preferably 2 to 20 nm, and more preferably 5 to 10 nm.

[0191] The content of inorganic fine particles is, for example, preferably 0% by mass or more and 60% by mass or less, more preferably 10% by mass or more and 50% by mass or less, more preferably 20% by mass or more and 40% by mass or less, and particularly preferably 20% by mass or more and 28% by mass or less. The content of inorganic binder is, for example, preferably 20% by mass or more and 70% by mass or less, more preferably 30% by mass or more and 50% by mass or less. The content of photocatalyst fine particles is, for example, preferably 10% by mass or more and 50% by mass or less, more preferably 20% by mass or more and 40% by mass or less. The anti-fogging layer may not contain inorganic fine particles, but may contain inorganic binder and photocatalyst fine particles.

[0192] The thickness of the anti-fogging layer is, for example, preferably 10 to 500 nm, more preferably 20 to 250 nm, and more preferably 50 to 200 nm. In particular, the thickness of the anti-fogging layer is preferably not more than twice the particle diameter of the inorganic fine particles. If the thickness of the anti-fogging layer is more than twice the particle diameter of the inorganic fine particles, the inorganic fine particles may overlap in the thickness direction, weakening the adhesion between the inorganic fine particles and possibly weakening the scratch resistance.

[0193] <3-5-2. Optical properties of transparent laminates> The visible light transmittance of the cover member having the above-mentioned anti-fogging layer is preferably 85% or more, more preferably 88% or more. In particular, the minimum value of the transmittance in the visible light wavelength range is preferably within 5% of the transmittance of the substrate, more preferably within 2%. On the other hand, the visible light reflectance of the cover member is preferably 10% or less, more preferably 7% or less. In particular, the maximum value of the reflectance in the visible light wavelength range is preferably within 5% of the reflectance of the substrate, more preferably within 2%. Furthermore, it is preferable that the reflectance of this cover member in the visible light wavelength range satisfies 1≦maximum reflectance / minimum reflectance≦1.5. The reflection curve affects the color of the transparent laminate. That is, if the reflectance at a certain wavelength is high, the cover member will be colored, which may not be acceptable depending on the application, but the color can be suppressed by satisfying the above-mentioned formula. The maximum reflectance / minimum reflectance can be adjusted by changing the film thickness and composition of the anti-fogging layer.

[0194] The haze ratio of this transparent laminate is preferably 1.0 or less, more preferably 0.5 or less, and particularly preferably 0.3 or less, making it suitable for use as a cover member for cameras and the like.

[0195] <3-6. Other aspects of the anti-fogging layer> In the above example, the anti-fog layer is directly laminated on the substrate 1, but an anti-fog sheet can also be attached. The anti-fog sheet includes a transparent substrate film in a sheet form, the anti-fog layer laminated on one side of the substrate film, and a transparent adhesive layer laminated on the other side of the substrate film. Then, by fixing the adhesive layer to the first main surface 11 of the substrate 1, the anti-fog sheet can be fixed.

[0196] The base film can be formed of a transparent resin sheet such as polyethylene, polyethylene terephthalate, etc. The thickness of the base film can be, for example, 75 to 100 μm. The adhesive layer can be formed of, for example, an acrylic or silicone adhesive layer.

[0197] It is also possible not to use a substrate film. First, a release film is prepared, and an anti-fog layer and an adhesive layer are laminated in this order on the release film. Then, the adhesive layer is attached to the first main surface 11 of the substrate 1, and the release film is removed, so that the adhesive layer and the anti-fog layer are laminated in this order on the substrate 1. Therefore, in this embodiment, the substrate film is not necessary, and distortion caused by the substrate film can be eliminated. It is also possible to attach a protective film on the adhesive layer, and then, when using, to attach the adhesive layer to the substrate after removing the protective film.

[0198] <3-7. Surface roughness> The surface roughness Ra of the anti-fog layer can be, for example, 1 to 1000 nm, and more preferably 10 to 1000 nm. By making the surface roughness Ra 1 nm or more, an anti-reflection effect can be obtained. In particular, the anti-reflection effect is large in the visible light band having a light wavelength of 400 to 800 nm. However, if the surface roughness Ra is more than 1000 nm, light scattering may occur, which is not preferable.

[0199] <4.Applications> The above-mentioned cover member can be used for various purposes. For example, as shown in FIG. 2, it can be used as a cover member 10 that covers the lens 51 of the imaging device 5. In this case, a bracket 6 for mounting to the lens can be appropriately attached to the above-mentioned cover member 10. Then, a closed space is formed in front of the lens by the cover member 10 and the bracket 6. In this case, the first main surface 11 of the base material 1 of the cover member 10 faces this closed space. Therefore, since the first functional layer 2 is laminated on the first main surface 11, it is possible to suppress the first main surface 11 from fogging due to the temperature difference or air pressure difference between the closed space and the outside. Therefore, it is possible to prevent the cover member 10 from fogging up and causing problems in photography.

[0200] Such an imaging device may be, for example, a bullet-type or dome-type surveillance camera, as shown in Fig. 3, in which the imaging device 5 is installed in a housing 7 and is shielded from the outside air by the housing 7 and a cover member 10. In this case, the cover member 10 is disposed in front of the lens of the imaging device 5. In such a surveillance camera, a temperature difference occurs on either side of the cover member 10 due to heat generated by the imaging device 5 and changes in the surrounding environment. Therefore, the cover member 10 is in an environment where condensation and fogging are likely to occur.

[0201] In addition, in imaging devices mounted on aircraft, where the atmospheric pressure changes significantly in the surrounding environment, condensation is likely to occur due to changes in atmospheric pressure. For the above reasons, the cover member 10 of the present embodiment can be suitably used as a cover member for surveillance cameras and devices mounted on aircraft.

[0202] In addition, the present invention is not limited to applications in places where the environment changes greatly as described above, but can also be used as a cover member for an imaging device mounted on a moving object such as an automobile, or as a cover member for other general imaging devices.

[0203] In particular, the transparent laminate having an anti-fog layer mainly composed of the above-mentioned inorganic compound, as described below, is excellent not only in anti-fog performance but also in peeling of the anti-fog layer, weather resistance, and water resistance, and can be suitably used as a cover member for various cameras such as surveillance cameras used outdoors. Furthermore, if the anti-fog layer contains photocatalytic fine particles, when irradiated with ultraviolet light, organic dirt attached to the surface of the anti-fog layer can be decomposed, and the anti-fog performance can be restored. As such a cover member, the anti-fog layer may be laminated on either side of the substrate. That is, it may be on either the lens side or the external side of the camera. When the anti-fog layer is laminated on the lens side of the camera, it is preferable to provide an irradiation device for irradiating ultraviolet light toward the anti-fog layer in the surveillance camera. This allows the organic dirt attached to the anti-fog layer to be forcibly decomposed when necessary.

[0204] <5.Other> In the above example, the first main surface 11 of the substrate 1 faces the camera lens side of the imaging device, so that the second main surface 12 is exposed to the outside air. Therefore, in order to prevent water droplets from adhering to the second main surface 12, for example, a water-repellent layer or a hydrophilic layer (third functional layer) can be formed on the second main surface 12. The water-repellent layer and the hydrophilic layer can be formed by coating a known water-repellent film or hydrophilic film. This point is the same in the second embodiment described later.

[0205] [Example] (1. Anti-fogging layer made of organic-inorganic composite film) Hereinafter, examples according to the first embodiment will be described, which have an anti-fogging layer made of an organic-inorganic composite film as the first functional layer, although the present invention is not limited to the following examples.

[0206] As Example 1, the following cover member was produced. (1) Base material: Float glass with a thickness of 1.1 mm was used. (2) First functional layer: The anti-fogging layer described below was formed on the first main surface of the substrate.

[0207] (i) Preparation of coating solution for anti-fog layer A polyvinyl acetal resin-containing solution (Sekisui Chemical Co., Ltd. "S-LEC KX-5", solid content 8 mass%, acetalization degree 9 mol%, containing an acetal structure derived from benzaldehyde) 62.5 mass%, n-hexyltrimethoxysilane (HTMS, Shin-Etsu Chemical Co., Ltd. "KBM-3063") 0.37 mass%, tetraethoxysilane (TEOS, Shin-Etsu Chemical Co., Ltd. [KBE-04]) 1.04 mass%, alcohol solvent (Nippon Alcohol Industry Co., Ltd. "Solmix AP-7") 20.44 mass%, purified water 15.63 mass%, hydrochloric acid 0.01 mass% as an acid catalyst, and leveling agent (Shin-Etsu Chemical Co., Ltd. "KP-341") 0.01 mass% were placed in a glass container and stirred at room temperature (25°C) for 3 hours to prepare a coating solution for forming an anti-fog layer.

[0208] (ii) Anti-fogging layer deposition process First, the coating liquid for the anti-fogging layer prepared as above was applied to the substrate, and the substrate was passed through a heating furnace at 90° C. for 5 minutes. Next, the substrate was immersed in water at 50° C. for 10 minutes, and heated in a heating furnace at 110° C. for 10 minutes. Thus, a moisture-absorbing layer of the anti-fogging layer was formed.

[0209] Next, polyether-modified dimethylsiloxane (BYK-333 manufactured by BYK Japan Co., Ltd.) was diluted with an alcohol-mixed solvent ("Solmix AP-7" manufactured by Japan Alcohol Sales Co., Ltd.) to 1 wt% to prepare a coating solution, which was applied by a flow coating method so that the entire water-supplying film of the tilted substrate was wet, and then dried as it was. In this way, a hydrophilic layer was formed. The film thickness of the hydrophilic layer was 10 nm.

[0210] (2. Anti-fogging layer mainly composed of inorganic compounds) Next, an example of a cover member having an anti-fogging layer containing an inorganic compound as a main component as a first functional layer will be described.

[0211] A float glass with a thickness of 1.1 mm was prepared as a substrate, and an anti-fogging layer having the following composition was formed on one side of the substrate: The anti-fogging layer was formed by applying a coating liquid for the anti-fogging layer by spin coating (rotation speed: 3000 rpm), and then baking under the following conditions.

[0212] [Table 1]

[0213] The cover members according to Examples 1 to 11 formed as described above were subjected to the following tests. (2-1. Anti-fogging performance test) Hot water at 80 to 100° C. was stored in a container, and a cover member was placed 5 cm from the surface of the hot water with the anti-fogging layer facing the water surface. A: A uniform water film is formed on the anti-fogging layer within 3 to 5 seconds. B: A water film is formed on the anti-fogging layer within 3 to 5 seconds, but distortion is observed. C: The anti-fog layer becomes foggy within 3 seconds.

[0214] Also, 60mW / cm 2 After irradiating the film with ultraviolet light for 10 minutes, the anti-fogging performance test was carried out again. The results are as follows: [Table 2]

[0215] In Examples 4 to 6, the content of SiO2 fine particles is low, which is thought to result in low anti-fogging performance. However, after irradiation with ultraviolet light, the dirt on the surface is decomposed, and anti-fogging performance similar to that of Examples 1 to 3 and 7 to 11 is obtained, and it is thought that this is sufficient for practical use. 2 The ultraviolet rays of 1 mW / cm2 have a higher intensity than sunlight, but this was an accelerated test. 2 Even with UV rays of It is considered that anti-fogging performance can be obtained if the film is irradiated for a period of time over this period in Examples 4 to 6. This point is the same in the tests described below.

[0216] (2-2. Abrasion test) A cloth made by Toray Industries, Inc., impregnated with alcohol (A-10 made by Futaba Chemical Co., Ltd.) was prepared, and this cloth was pressed against the anti-fogging layer of each example with a load of 300 g, and made to go back and forth 10 times over a distance of 5 cm. Then, the above-mentioned anti-fogging performance test was performed, and it was visually confirmed whether or not the anti-fogging layer had peeled off. In addition, at 60 mW / cm 2 of ultraviolet rays After 20 minutes of irradiation, the anti-fog performance test was carried out again, with the following results: [Table 3]

[0217] In Examples 1 to 3, peeling of the anti-fogging layer was confirmed by the abrasion test. This is believed to be due to the high content of SiO2 fine particles. However, even if the content of SiO2 fine particles is high as in Examples 7 to 9, when the material is baked at a high temperature, it is believed that a strong anti-fogging layer is formed with sufficient cross-linking of the SiO2 fine particles, and peeling is not observed. Therefore, it was found that, for example, even if the anti-fogging layer is wiped to remove dirt, peeling of the anti-fogging layer is prevented, particularly in Examples 4 to 11.

[0218] Regarding the anti-fogging performance, it is considered that the baking temperature is low in Examples 1 to 6, so that the organic matter contained in the SiO2 binder remains on the surface of the anti-fogging layer, resulting in a high contact angle on the surface, and thus the anti-fogging performance is not exhibited. On the other hand, it is considered that the baking temperature is high in Examples 7 to 11, so that the organic matter contained in the SiO2 binder is removed from the surface by thermal decomposition, and thus the anti-fogging performance is exhibited. In addition, in such durability tests, it is considered that the anti-fogging performance is deteriorated due to the adhesion of hydrocarbons to the surface of the anti-fogging layer and the organic matter residue from the SiO2 binder coming out to the surface of the anti-fogging layer, which contaminates the anti-fogging layer.

[0219] (2-3. Weather resistance test) The cover members according to the respective examples were stored in a thermostatic chamber at a temperature of 80° C. and a humidity of 80% for 48 hours. Then, the above-mentioned anti-fogging performance test was carried out. 2 The time until the anti-fogging performance of the above-mentioned evaluation A was exhibited was measured. The evaluation regarding this time is as follows. P: Less than 10 hours Q: 10 to 30 hours R: More than 30 hours The results are as follows: [Table 4]

[0220] In the anti-fogging performance test after removing the cover member from the thermostatic chamber, all of Examples 1 to 11 had low anti-fogging performance (evaluation C). On the other hand, after irradiation with ultraviolet light, the anti-fogging performance was high in Examples 1 to 3 and 7 to 11, but the anti-fogging performance remained low in Examples 4 to 6. This is considered to be due to the high content of inorganic binder. In addition, the present inventors found that in Examples 1 to 3, although not detailed in Table 4, the higher the content of TiO2 fine particles, the shorter the time until anti-fogging performance was developed. That is, the time until anti-fogging performance was developed after ultraviolet light irradiation was shorter in Examples 2 and 3 than in Example 1. Therefore, for example, when the present invention is used as a cover member for a surveillance camera, it was found that it generally exhibits high anti-fogging performance if ultraviolet light is irradiated even in an outdoor environment of high temperature and high humidity.

[0221] (2-4. Immersion test) The cover members according to the respective examples were immersed in water (20° C.±5° C.) for 180 hours. Thereafter, the above-mentioned anti-fogging performance test was carried out. The results are as follows. [Table 5]

[0222] The ratings of "A, B" for Examples 1 to 5 indicate that the anti-fog layer includes a region rated B, but all of them have high anti-fog performance. Therefore, the cover member according to the present invention is considered to be suitable for outdoor use where it is exposed to rainwater.

[0223] From the above test results, all of Examples 1 to 11 are suitable for outdoor use. In particular, Examples 8 to 11 have high anti-fogging performance even in harsh environments.

[0224] (2-5. Transmittance) The transmittance of the cover members and substrate of Examples 1 to 3 was measured based on JIS R3106. The results are shown in Figure 4. As shown in Figure 4, in the visible light wavelength range (approximately 380 to 780 nm), Examples 1 to 3 exhibit a transmittance of approximately 89% or more. In particular, considering that the transmittance of the substrate, which is a glass plate, is approximately 91%, Examples 1 to 3 are found to exhibit high transmittance, falling within 2% of the transmittance of the substrate.

[0225] (2-6. Reflectance) The reflectance of the cover members and substrate of Examples 1 to 3 was measured based on JIS R3106. The results are shown in Figure 5. As shown in Figure 5, in the visible light wavelength range (approximately 380 to 780 nm), Examples 1 to 3 exhibit a reflectance of approximately 6 to 8%. In particular, considering that the reflectance of the substrate, which is a glass plate, is approximately 8 to 9%, Examples 1 to 3 were found to exhibit low reflectance, being approximately 2% lower than the reflectance of the substrate.

[0226] (3. Anti-fogging layer with hydrophilic function) Next, Examples 12 to 20 of the cover member in which the above-mentioned anti-fogging layer having a hydrophilic function is formed as the first functional layer will be described.

[0227] A float glass with a thickness of 1.1 mm was prepared as a substrate, and an anti-fogging layer was formed on one side of the substrate. The anti-fogging layer was formed by applying a coating liquid for the anti-fogging layer described below by spin coating, cooling with air for 10 minutes, and then baking in a heating furnace. In the heating furnace, baking was performed at 100°C for 30 minutes. After that, the anti-fogging layer was formed by cooling with air at room temperature. The thickness of the anti-fogging layer was about 10 μm.

[0228] The coating liquid for the anti-fog layer was prepared as follows: polyvinyl acetal resin-containing solution (Sekisui Chemical Co., Ltd.'s "S-LEC KX-5", 60.24 mass% (solid content concentration 5.0 mass%), high boiling point solvent (shown in Table 6) 20.0 mass%, 3-glycidoxypropyltrimethoxysilane (GPTMS, Shin-Etsu Chemical Co., Ltd.'s "KBM-403") 0.28 mass% (solid content concentration 0.2 mass%), tetraethoxysilane (TEOS, Shin-Etsu Chemical Co., Ltd.'s "KBE-04") 1.04 mass% (solid content concentration 0.30 mass%), alcohol solvent ( 6.32% by mass of "Solmix AP-7" manufactured by Nippon Alcohol Industry Co., Ltd., 11.87% by mass of purified water, 0.10 to 0.40% by mass of surfactant (NOF Corporation's "Rapisol") (solid content concentration 0.10 to 0.40% by mass, see Table 6), 0.01% by mass of hydrochloric acid as an acid catalyst, 0.01% by mass of leveling agent (Shin-Etsu Chemical Co., Ltd.'s "KP-341"), 0.01% by mass of leveling agent (Shin-Etsu Chemical Co., Ltd.'s "KP-112"), 0.01% by mass of leveling agent (Dow Chemical Japan's "DOWSIL8526 Additive"), and 0.01% by mass of leveling agent (BYK Japan's "BKY-349") were placed in a glass container and stirred at room temperature (25°C) for 3 hours to prepare a coating solution for the anti-fog layer.

[0229] As the high boiling point solvent, propylene glycol (PG), polyethylene glycol (PEG), and triethylene glycol (TEG) were used. The coating solutions for the anti-fogging layer according to Examples 12 to 20 contained the following high boiling point solvents (unit: mass % of the addition ratio).

[0230] [Table 6]

[0231] The anti-fogging layer formed as above was subjected to the following tests.

[0232] (3-1 Anti-fogging performance test) Hot water at 80 to 100 °C was stored in a container, and a cover member with an anti-fog layer facing the water surface side was placed at a position 5 cm from the water surface of this hot water. Then, it was inspected whether it would not fog up for 10 seconds or more (anti-fog performance), whether a water film was formed within 1 second, and whether there were any problems with the appearance. In the appearance inspection, it was visually inspected whether the surface of the anti-fog layer was smooth and whether there were no distortions or streaks formed. The results are as follows, where OK indicates that there were no problems.

Table 7

[0233] From the above results, it was found that the anti-fog layers according to Examples 12 to 20 exhibited sufficient anti-fog performance.

[0234] (3-2 Abrasion test) As the cloth, Terylene manufactured by Toray Industries, Inc. impregnated with alcohol (A-10 manufactured by FUTABA CHEMICAL INDUSTRIES CO., LTD.) was prepared. This cloth was pressed against the anti-fog layer of each example with a load of 300 g, and reciprocated 10 times over a distance of 5 cm. Then, the same anti-fog performance test as described in (3-1) above was conducted. The results are as follows.

Table 8

[0235] From the results in Table 8, after wiping, in Examples 15, 16, 18, and 20, distortions were observed on the surface of the anti-fog layer, but in the other examples, the anti-fog performance was maintained.

[0236] (3-3. Weather resistance test) The cover members according to each example were placed in a thermostatic chamber at a temperature of 85 °C and a humidity of 85% for 48 hours. Then, the same anti-fog performance test as described in (3-1) above was conducted. The results are as follows.

Table 9

[0237] <B. Second Embodiment> A second embodiment in which the transparent laminate according to the present invention is applied to a cover member will be described below with reference to the drawings. Fig. 6 is a cross-sectional view of the cover member according to the second embodiment.

[0238] The cover member 20 according to this embodiment differs from the first embodiment in that a second functional layer 3 is further laminated on the above-mentioned first functional layer 2, and the other configurations are as described in the first embodiment. The second functional layer will be described below.

[0239] <1. Overview of cover material> 6, the cover member 20 according to this embodiment includes a substrate 1, a first functional layer 2 laminated on a first main surface 11 of the substrate 1, and a second functional layer 3 laminated on the first functional layer 2. The substrate 1 and the first functional layer 2 are the same as those shown in the first embodiment.

[0240] For example, an anti-reflection film, an anti-glare film, an antistatic film, an antibacterial film, etc. can be used as the second functional layer 3. In the following, an example in which an anti-fogging layer is used as the first functional layer 2 and an anti-reflection layer is used as the second functional layer 3 will be described.

[0241] The anti-fogging layer of the first functional layer 2 does not have a hydrophilic layer on the top surface as shown in the first embodiment, but is, for example, a moisture absorbing layer formed of an organic-inorganic composite anti-fogging layer. If an anti-reflection layer is laminated on such a moisture absorbing anti-fogging layer, the moisture absorbing effect may be hindered. Therefore, the anti-reflection layer according to this embodiment has voids inside, forming a passage for water vapor to the anti-fogging layer 2. This will be described in detail below.

[0242] <2.Second functional layer> FIG. 7 is a cross-sectional view of the second functional layer. As shown in FIG. 6, the second functional layer 3 includes hollow particles 31 and a binder 32. The hollow particles 31 are made of a material having a refractive index of 1.15 to 2.70. The binder 32 is formed of at least polysilsesquioxane and binds the hollow particles 31. In the second functional layer 3, the absorbance derived from a hydrocarbon group not directly bonded to a silicon atom, the absorbance derived from a bond between a silicon atom and a non-reactive functional group, and the absorbance derived from a bond between a silicon atom and a hydroxyl group, which are determined by an attenuated total reflection measurement method (ATR method) using a Fourier transform infrared spectrophotometer, are represented as Ia, Ib, and Ic, respectively. The second functional layer 3 satisfies at least one of the conditions Ib / Ia≧0.7 and Ib / Ic≧0.3. In this specification, Ib / Ia is also referred to as the organic / inorganic parameter (D), and Ib / Ic is also referred to as the hydrophobic parameter (H). The absorbance Ia, absorbance Ib, and absorbance Ic can be determined, for example, from an absorption spectrum obtained by the ATR method according to the method described in the Examples.

[0243] The organic-inorganic parameter (D) increases as the amount of hydrocarbon groups not directly bonded to silicon atoms contained in the binder 32 decreases. When the amount of hydrocarbon groups not directly bonded to silicon atoms contained in the binder 32 is small, the Si-O-Si network in the binder 32 is dense, and the density of the inorganic component in the binder 32 increases. As a result, the hollow particles 31 are firmly fixed by the Si-O-Si network. Therefore, if Ib / Ia≧0.7 in the second functional layer 3, the hollow particles 31 are firmly fixed in the second functional layer 3, and the second functional layer 3 has properties advantageous for low refractive index coating. If the hollow particles are not sufficiently fixed in the film, the mechanical strength of the film may decrease.

[0244] The hydrophobic parameter (H) increases as the number of hydroxyl groups bonded to silicon atoms in the binder 32 decreases. For example, when hydroxyl groups condense with each other in the raw material of the binder 32 to form a network of Si-O-Si, the number of hydroxyl groups bonded to silicon atoms in the binder 32 decreases. If the hydrophobic parameter (H) is a predetermined value or more, a network of Si-O-Si develops densely in the binder 32, and the hollow particles 31 can be firmly fixed by this network. Therefore, if Ib / Ic≧0.3 in the second functional layer 3, the hollow particles 31 are firmly fixed in the second functional layer 3, and the second functional layer 3 has properties advantageous for low refractive index coating.

[0245] The second functional layer 3 preferably further satisfies the conditions of Ib / Ia≧0.7 and Ib / Ic≧0.3, so that the hollow particles 31 are more reliably and firmly fixed in the second functional layer 3, and the second functional layer 3 has properties advantageous for low refractive index coating.

[0246] When silanol groups (Si-OH) are present in the binder 32, the silanol groups form hydrogen bonds with the silanol groups present on the surface of the glass plate 1, resulting in high affinity. For this reason, a film having a hydrophobic parameter (H) equal to or less than a predetermined value also easily adheres to the glass plate 1. The second functional layer 3 more desirably satisfies the condition 0.3≦Ib / Ic≦2.0 so as to exhibit good adhesion to both substrates having hydrophilic and hydrophobic surfaces.

[0247] In the second functional layer 3, the first absorbance, the second absorbance, and the third absorbance, which are determined by the ATR method and originate from the bond between one oxygen atom and two silicon atoms, are represented as Id, Ie, and If, respectively. The first absorbance Id corresponds to a first wavenumber. The second absorbance Ie corresponds to a second wavenumber that is greater than the first wavenumber. The third absorbance If corresponds to a third wavenumber that is greater than the second wavenumber. The second functional layer 3 preferably satisfies at least one of the conditions Id / Ib≦60, Ie / Ib≦20, and If / Ib≦174. In this specification, Id / Ib is also referred to as the first network parameter (N1), Ie / Ib is also referred to as the second network parameter (N2), and If / Ib is also referred to as the third network parameter (N3).

[0248] The first wave number is, for example, 455±50 cm -1 The second wavenumber is, for example, 780±50 cm -1 The third wavenumber is, for example, 1065±50 cm -1 This is the wavenumber at which the maximum value of the absorption spectrum appears.

[0249] The first network parameter (N1), the second network parameter (N2), and the third network parameter (N3) are larger as the number of bonds (Si-O-Si) between oxygen atoms and two silicon atoms in the binder 32 increases. The more the Si-O-Si network formed by condensation of hydroxyl groups in the raw material of the binder 32 develops, the larger the first network parameter (N1), the second network parameter (N2), and the third network parameter (N3) are. On the other hand, in order to maintain good film formability, it is important to suppress the aggregation of hollow particles and maintain a uniform thickness of the coating film. In order to suppress the aggregation of hollow particles, it is desirable to prevent excessive development of the Si-O-Si network. From this viewpoint, it is desirable that the second functional layer 3 satisfies at least one of N1 being 60 or less, N2 being 20 or less, and N3 being 174 or less. This allows the second functional layer 3 to be formed satisfactorily, and the second functional layer 3 can provide an antireflection structure having good antireflection performance.

[0250] More desirably, the second functional layer 3 further satisfies the conditions Id / Ib≦60, Ie / Ib≦20, and If / Ib≦174.

[0251] Typically, the polysilsesquioxane of the binder 32 has a non-reactive functional group bonded to a silicon atom. In order for the polysilsesquioxane of the binder 32 to exhibit an appropriate hydrophobic effect, the non-reactive functional group is, for example, a functional group exhibiting hydrophobicity, such as an alkyl group. Desirably, the polysilsesquioxane of the binder 32 is a polysilsesquioxane in which a hydrocarbon group containing 16 or less carbon atoms is bonded to a silicon atom as a non-reactive functional group. In this case, since the non-reactive functional group is not bulky, a dense Si-O-Si network is easily formed.

[0252] The binder 32 may further be formed of, for example, silica. In this case, the polysilsesquioxane contained in the binder 32 tends to exert a hydrophobic effect, and the silica contained in the binder 32 tends to exert a hydrophilic effect. Therefore, by adjusting the ratio (Mp / Ms) of the amount of substance Mp of polysilsesquioxane to the amount of substance Ms of silica in the binder 32, the hydrophilicity or hydrophobicity of the second functional layer 3 can be adjusted to an appropriate level. This allows the second functional layer 3 to be appropriately formed on a substrate having a hydrophilic surface such as a glass substrate, and the second functional layer 3 to be appropriately formed on a substrate having a hydrophobic surface such as a resin. From this viewpoint, the ratio (Mp / Ms) of the amount of substance Mp of polysilsesquioxane to the amount of substance Ms of silica in the binder 32 is, for example, 3 / 7 or more, preferably 1 to 9, and more preferably 3 / 2 to 4.

[0253] The hollow particles 31 are not particularly limited as long as they have a hollow structure, and may have, for example, a spherical, cylindrical, or sheet-like shape. The hollow particles 31 have, for example, an average particle diameter (primary particle diameter) of 10 to 150 nm. This makes it easy for the hollow particles 31 to be uniformly dispersed in the second functional layer 3. The average particle diameter of the hollow particles 31 can be determined, for example, by arithmetically averaging the particle diameters of 50 or more hollow particles 31 observed using a transmission electron microscope (TEM) or a scanning electron microscope (SEM). Note that the particle diameter of each particle means the maximum diameter.

[0254] The hollow particles 31 preferably have an average particle diameter of 20 to 100 nm, more preferably 30 to 70 nm. The maximum dimension of the internal space in the hollow particles 31 is, for example, 5 to 100 nm, preferably 10 to 70 nm, more preferably 20 to 50 nm. The hollow particles 31 are preferably monodisperse particles having a coefficient of variation of 0.1 or less.

[0255] The material of the hollow particles 31 may be an inorganic material or an organic material as long as it has a refractive index of 1.15 to 2.70. The material of the hollow particles 31 is preferably a material having a refractive index of 1.20 to 2.00, more preferably a material having a refractive index of 1.30 to 1.50, and even more preferably a material having a refractive index of 1.38 to 1.46. From the viewpoint of resistance to deformation due to an external force, the hollow particles 31 are preferably made of an inorganic material. In this case, the hollow particles 31 are made of at least one selected from the group consisting of, for example, silica, magnesium fluoride, alumina, aluminosilicate, titania, and zirconia.

[0256] In particular, the hollow particles 31 are preferably made of silica or magnesium fluoride in order to provide an antireflection structure having high antireflection performance by a low refractive index coating using the second functional layer 3. The refractive index of silica is 1.46, and the refractive index of magnesium fluoride is 1.38.

[0257] The structure and material of the hollow particles 31 are determined so that the hollow particles 31 have a desired refractive index. For example, the material of the hollow particles 31 and the ratio of the internal space to the total volume of the hollow particles 31 are determined so that the hollow particles 31 have a desired refractive index. The hollow particles 31 have a refractive index of, for example, 1.10 to 1.40, preferably 1.20 to 1.35, and more preferably 1.25 to 1.30. For example, in a plurality of types of hollow particles made of materials having different refractive indexes, when the ratio of the internal space to the total volume of the hollow particles is the same, hollow particles made of a material with a low refractive index have a lower refractive index than hollow particles made of a material with a high refractive index.

[0258] The refractive index of the hollow particles 31 can be measured, for example, by the immersion method (Becke line method). For example, when the hollow particles 31 are made of silica, the refractive index of the hollow particles 31 can be measured according to the following procedure. (i) The dispersion medium of the dispersion liquid of the hollow particles 31 is evaporated and dried to obtain a powder. (ii) The powder obtained in (i) is mixed with various standard refractive index liquids having different refractive indexes, such as Series A and Series AA manufactured by GARGILL. (iii) The refractive index of the standard refractive index liquid used when the mixed liquid obtained in (ii) becomes transparent is determined as the refractive index of the hollow particles 31.

[0259] The hollow particles 31 may be commercially available or may be prepared by a predetermined method. For example, the hollow particles 31 may be prepared by forming a shell around a core and then removing the core. For example, a shell made of silica or a shell made of magnesium fluoride is formed around a polymer core having a particle diameter of several tens of nanometers. The polymer core is then removed by dissolving in a solvent or by burning to obtain hollow particles 31 that are hollow silica particles or hollow magnesium fluoride particles. Alternatively, a shell made of magnesium fluoride may be formed around a core made of silica, and the silica core may be dissolved in an alkali to obtain a hollow particle 31. By dissolving the mixture, hollow particles 31 which are hollow magnesium fluoride particles can be obtained.

[0260] In the second functional layer 3, the ratio (Wh / Wb) of the mass Wh of the hollow particles 31 to the mass Wb of the binder 32 is, for example, 1 / 5 to 20, preferably 1 / 3 to 10, and more preferably 1 to 5. This makes it possible to provide an antireflection structure with high antireflection performance by the low refractive index coating using the second functional layer 3.

[0261] The thickness of the second functional layer 3 is not particularly limited, but is determined, for example, according to the wavelength of light to be prevented from being reflected. Specifically, the thickness of the second functional layer 3 is set so that the optical film thickness (refractive index x physical film thickness) satisfies λ / 4 when the central wavelength of the wavelengths of light to be prevented from being reflected is λ (nm). For example, in order to prevent the reflection of light belonging to the visible light region (practically, wavelengths of 380 nm to 780 nm), the optimal physical film thickness is 115 nm when the central wavelength λ is λ=550 nm and the refractive index of the low refractive index film used is 1.20. The thickness of the second functional layer 3 that is practically effective for preventing the reflection of visible light is 50 to 300 nm, preferably 70 to 200 nm, and more preferably 90 to 170 nm. As a result, an antireflection structure having high antireflection performance can be provided by the low refractive index coating using the second functional layer 3. In addition, in order to prevent reflection of light with a central wavelength of λ=850 nm, which is close to the visible light region in the near infrared region (for example, wavelengths of 800 nm to 2500 nm), the optimal physical film thickness is 177 nm when the refractive index of the low refractive index film used is 1.20. The thickness of the second functional layer 3 that is practically effective for preventing reflection of near infrared rays is 80 to 350 nm, preferably 130 to 250 nm, and more preferably 150 to 220 nm. This makes it possible to provide an antireflection structure with high antireflection performance by the low refractive index coating using the second functional layer 3. When a multilayer film is used as the antireflection structure, a low refractive index layer with a film thickness of 50 nm or less may be used. In addition, the physical film thickness of the low refractive index film is not limited to these, but its cross section can be measured by SEM, TEM, ellipsometer, etc.

[0262] The second functional layer 3 has a refractive index of, for example, 1.45 or less, preferably 1.1 to 1.35. This allows a low refractive index coating using the second functional layer 3 to provide an antireflection structure with high antireflection performance. The second functional layer 3 desirably has a refractive index of 1.30 or less, more desirably has a refractive index of 1.25 or less. From the viewpoint of reducing the refractive index of the second functional layer 3, the second functional layer 3 may include an air space in the space between the hollow particles 31 or in the binder 32. The refractive index of the second functional layer 3 can be determined, for example, by reflectance spectroscopy. By increasing the ratio of this air space (void ratio), the refractive index of the second functional layer 3 can be reduced. The void ratio is, for example, 0 to 70 vol%, preferably 10 to 50 vol%, and more preferably 20 to 50 vol%. This point is the same for the second functional layer consisting of multiple layers described later.

[0263] The second functional layer 3 is, for example, a cured product obtained by curing a specific liquid composition. This liquid composition contains hollow particles, polysilsesquioxane, and a solvent. The hollow particles are made of a material having a refractive index of 1.15 to 2.70. In the cured product obtained by applying the liquid composition to a substrate and curing the liquid composition, at least one of the conditions Ib / Ia≧0.7 and Ib / Ic≧0.3 is satisfied. The solvent contained in the liquid composition is, for example, an alcohol such as ethanol, methanol, 1-propanol, or 2-propanol, or water.

[0264] The solution for the second functional layer can be applied to the anti-fog layer, which is the first functional layer, by various methods such as spin coating, roll coating, and spray coating. However, methods such as roll coating and spray coating require time from application to baking, for example, because leveling of the solution is required between application and baking. Therefore, the solvent may evaporate during this time, and drying may proceed unevenly. This may cause, for example, a difference in refractive index or film thickness between the area where the solvent has evaporated before forming a network in a heating furnace and the area where the solvent remains at the time of forming the network in the binder.

[0265] Therefore, when coating at such high temperatures, it is preferable to use a high boiling point solvent. This can suppress the volatilization of the solvent in the solution for the second functional layer, so that the refractive index and film thickness of the film can be made uniform. In addition, since the formation of the network in the binder occurs by a dehydration condensation reaction, etc., a baking temperature of about 100 ° C is preferable. Therefore, it is preferable that the boiling point of the high boiling point solvent is 100 ° C or higher. In addition, since the first functional layer contains an organic resin, yellowing may occur at 300 ° C or higher. Therefore, it is preferable that the baking temperature of the second functional layer is 300 ° C or lower. In contrast, if a solvent with a boiling point of 300 ° C or higher is used, there is a risk that a large amount of the solvent will remain after baking. As a result, the refractive index of the second functional layer may change, and the desired optical properties may not be obtained. Therefore, it is preferable that the boiling point of the high boiling point solvent is 100 ° C or higher and 300 ° C or lower.

[0266] The high boiling point solvent is not particularly limited, but may be, for example, 1-methoxy-2-propanol or 3-methoxy-3-methyl-1-butanol as the main component. In addition, such a high boiling point solvent is preferably present in a solution at a concentration of, for example, 1 ppb or more, 5 g / cm or more. 3 It is preferable that the content is less than 3 g / cm 3 More preferably, it is 1 g / cm or less. 3 It is more preferable that the concentration of the solvent is 5 g / cm or less. The reason is as follows. In the solution for the second functional layer, a solvent having a temperature higher than the baking temperature is added, so that the solvent remains in the second functional layer at 1 ppb or more even after baking. Here, it is preferable that the concentration of the solvent is 5 g / cm or less in the second functional layer. 3 If the above solvents are included, the residual solvent may cause The refractive index will change, and the optical thin film may no longer function. Therefore, the solvent should be less than 5 g / cm 3It is preferable that the content of the high boiling point solvent in the second functional layer 3 is less than 100%. The volume of the second functional layer 3 is calculated from the average thickness of the second functional layer 3 measured at 10 points and the area of ​​the second functional layer 3. The amount of the high boiling point solvent is calculated by analysis using a gas chromatograph or the like. The concentration of the high boiling point solvent in the second functional layer 3 (g / cm3) is calculated from the calculated volume and amount of solvent. 3 ) is calculated.

[0267] In this liquid composition, since an organosilane compound having a fluoroalkyl group is not required, phase separation is unlikely to occur in the liquid composition, and the liquid composition is likely to be homogeneous. In addition, the liquid composition has high wettability to the substrate and the resin substrate, and the liquid composition is likely to provide an antireflection layer having a uniform structure.

[0268] In the above cured product, it is preferable that the conditions Ib / Ia≧0.7 and Ib / Ic≧0.3 are further satisfied.

[0269] In the above cured product, it is desirable that at least one of the following conditions is satisfied: Id / Ib≦60, Ie / Ib≦20, and If / Ib≦174.

[0270] In the above cured product, it is more preferable that the conditions Id / Ib≦60, Ie / Ib≦20, and If / Ib≦174 are further satisfied.

[0271] The polysilsesquioxane in the liquid composition is, for example, a polysilsesquioxane in which a hydrocarbon group containing 16 or fewer carbon atoms is attached to a silicon atom as a non-reactive functional group.

[0272] The characteristics of the hollow particles 31 in the second functional layer 3 typically also apply to the hollow particles in the liquid composition. Therefore, the hollow particles in the liquid composition have an average particle size (primary particle size) of, for example, 10 to 150 nm. In addition, the hollow particles in the liquid composition are preferably made of at least one selected from the group consisting of silica, magnesium fluoride, alumina, aluminosilicate, titania, and zirconia.

[0273] The liquid composition may contain, for example, silica in addition to the hollow particles.

[0274] The second functional layer 3 is formed, for example, by applying a liquid composition to the first functional layer 2 and curing the liquid composition. In this way, a low refractive index layer is formed using the second functional layer 3. By using the liquid composition, an organosilane compound having a fluoroalkyl group is not required, and low refractive index coating can be easily achieved.

[0275] The polysilsesquioxane of the liquid composition is formed, for example, by hydrolysis and dehydration condensation of a trifunctional alkoxysilane contained in the raw material of the liquid composition. When silica is contained in the liquid composition in addition to the hollow particles, the silica is formed, for example, by hydrolysis and dehydration condensation of a tetrafunctional alkoxysilane contained in the raw material of the liquid composition. For example, the tetrafunctional alkoxysilane forms silica (SiO2) by the reaction of the following (Formula 1) and (Formula 2). R a represents an alkyl group. Trifunctional alkoxysilanes can be converted to polysilsesquioxanes (R b SiO 3 / 2 ) is formed. R b indicates a non-reactive functional group, R c represents an alkyl group. Si(OR a )4+4H2O→Si(OH)4+4R a OH (Formula 1) Si(OH)4→SiO2+2H2O (Formula 2) R b Si(OR c )3+3H2O→R b Si(OH)3+3R c OH (Formula 3) R b Si(OH)3→R b SiO 3 / 2 +3 / 2H2O (Formula 4)

[0276] The hydrolysis catalyst contained in the raw material of the liquid composition is, for example, a carboxylic acid such as formic acid or acetic acid.

[0277] <3. Adjustment of refractive index> In order for the second functional layer 3 to function properly as an anti-reflection layer, it is necessary to determine the refractive index of the second functional layer 3 in consideration of the refractive index of the anti-fogging layer, which is the first functional layer 2. The refractive index of the anti-fogging layer is generally 1.5 to 1.6, depending on the material. It is known that in order to reduce the refractive index of the first functional layer 2 and the second functional layer 3 as a whole, the refractive index of the second functional layer 3 is set to the 1 / 2 power of the refractive index of the first functional layer 1. For example, when the refractive index of the anti-fogging layer is 1.55, it is preferable that the refractive index of the second functional layer 3 is 1.24.

[0278] As described above, the second functional layer 3 is composed of hollow particles 31, binder 32, and air layers, and since it contains hollow particles containing air, it is possible to lower the refractive index. Furthermore, since it also contains air layers, the refractive index can be further reduced by increasing the ratio (void fraction). Therefore, by adjusting the ratio of hollow particles and the void fraction, it is possible to set the refractive index of the second functional layer 3 to, for example, about ±0.1 of the 1 / 2 power of the refractive index of the first functional layer 2.

[0279] <4. Second functional layer consisting of multiple layers> In the above example, the second functional layer 3 is formed as a single layer, but it can also be formed as two layers. For example, as shown in FIG. 8, the second functional layer 3 can be composed of a first layer 301 laminated on the first functional layer 2 and a second layer 302 laminated on the first layer 301. Here, in order to reduce the refractive index of the functional layers 2 and 3 as a whole, the refractive index of the first layer 301 is made smaller than that of the antifogging layer 2, and the refractive index of the second layer 302 is made smaller than that of the first layer 301. The refractive index of the first layer 301 can be, for example, 1.35 to 1.55, and the refractive index of the second layer 302 can be, for example, 1.10 to 1.25.

[0280] As such an example, the second layer 302 is formed of the above-mentioned single-layer second functional layer 3. The first layer 301 is a layer obtained by removing the hollow particles 31 from the second layer 302, and is a layer made of at least one of polysilsesquioxane and silica constituting the binder. The second layer 302 may have a thickness of, for example, 30 to 300 nm. The first layer 301 does not contain hollow particles and does not contain an air layer, but water vapor passes through it because the binder 32 is porous. Therefore, even if such a first layer 301 is formed, water vapor reaches the anti-fogging layer 2 through the first layer 301 and the second layer 302. However, since water vapor is less likely to pass through it than through the second layer 302, it is preferable that the film thickness of the first layer 301 is thinner than that of the second layer 302.

[0281] In this way, when the second functional layer 3 is formed of multiple layers, the refractive index of each layer may be gradually decreased from the first functional layer 2 toward the outermost layer. Therefore, the second functional layer 3 may be formed of three or more layers.

[0282] <5. Properties of the second functional layer> When the first functional layer 2 is an anti-fogging layer, its volume may change due to moisture absorption. Since the second functional layer 3 is laminated on the first functional layer 2, it is preferable that the second functional layer 3 follows the change in volume of the first functional layer 2. If the second functional layer 3 does not follow the change in volume, cracks may occur in the second functional layer 3. Therefore, for example, if the anti-fogging layer 2 has a flexural modulus of 2 to 3 GPa, the second functional layer 3 has a flexural modulus in a range overlapping with the flexural modulus of the anti-fogging layer 2, for example, preferably 1 to 10 GPa, and more preferably 1 to 4 GPa. That is, polysilsesquioxane (flexural modulus of 2 to 3 GPa) showing the same flexural modulus as the anti-fogging layer 2 can be suitably used as a binder for the second functional layer 3.

[0283] Furthermore, since the first functional layer and the second functional layer may expand and contract due to temperature changes, it is preferable that the difference in the linear expansion coefficient between the first functional layer 2 and the second functional layer 3 is 30 ppm / ° C. For example, the linear thermal expansion coefficient of the anti-fogging layer is 60 to 84 ppm / ° C., whereas the linear thermal expansion coefficient of polysilsesquioxane is 40 to 70 ppm / ° C., and therefore it can be used as a binder for the second functional layer 3. In other words, even if the film volume increases or decreases due to the amount of water absorbed by the anti-fogging layer, cracks in the first functional layer 2 and the second functional layer 3 can be suppressed.

[0284] <6. Other aspects> The first functional layer 2 and the second functional layer 3 according to this embodiment can be in various forms. For example, when the second functional layer 3 is a single layer, as shown in FIG. 9, the anti-fogging layer 2 and the anti-reflection layer 3 are laminated in this order on the substrate film 81, and then the substrate film 81 can be attached to the substrate 1 via an adhesive layer (not shown). Similarly, when the second functional layer 3 is a multi-layered structure, as shown in FIG. 10, the anti-fogging layer 2, the first layer 301 of the anti-reflection layer, and the second layer 302 are laminated in this order on the substrate film 81, and then the substrate film 81 can be attached to the substrate 1 via an adhesive layer 82. The substrate film 81 and the adhesive layer 82 are the same as those shown in the first embodiment.

[0285] The transparent laminate of the present invention may contain an ultraviolet absorbing agent and / or an infrared absorbing agent. At least one of the first functional layer, the second functional layer, and the third functional layer may contain an ultraviolet absorbing agent and / or an infrared absorbing agent.

[0286] Alternatively, at least one of the above-mentioned substrate film, adhesive layer, and anti-fog layer may contain an ultraviolet absorbing agent and / or an infrared absorbing agent.

[0287] Examples of ultraviolet absorbents include benzotriazole compounds [2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole, etc.], benzophenone compounds [2,2',4,4'-tetrahydroxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone), etc.], and hydroxyphenyltriazines. Examples of the ultraviolet absorbent include organic substances such as compounds [2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-di-t-butylphenyl)-s-triazine, 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-s-triazine, 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-di-t-butylphenyl)-s-triazine, etc.] and cyanoacrylate compounds [ethyl-α-cyano-β,β-diphenylacrylate, methyl-2-cyano-3-methyl-3-(p-methoxyphenyl)acrylate, etc.]. The ultraviolet absorbent may be used alone or in combination of two or more kinds. The ultraviolet absorbent may also be at least one organic dye selected from polymethine compounds, imidazoline compounds, coumarin compounds, naphthalimide compounds, perylene compounds, azo compounds, isoindolinone compounds, quinophthalone compounds, and quinoline compounds. Among the ultraviolet absorbents, preferred are organic ultraviolet absorbents, more preferred are at least one selected from benzotriazole compounds, benzophenone compounds, hydroxyphenyltriazine compounds and cyanoacrylate compounds, and even more preferred are benzophenone compounds. Benzophenone compounds are preferred because they have good solubility in alcohol-based solvents contained in the coating liquid for forming the organic-inorganic composite anti-fogging film and disperse more uniformly in the polyvinyl acetal resin.

[0288] The ultraviolet absorbent preferably has a hydroxyl group, and more preferably has two or more hydroxyl groups bonded to one benzene skeleton of the ultraviolet absorbent. The ultraviolet absorbent is added in an amount of preferably 0.1 to 50 parts by weight, more preferably 1.0 to 40 parts by weight, and even more preferably 2 to 35 parts by weight, based on 100 parts by weight of the water absorbent resin.

[0289] Examples of the infrared absorbing agent include organic infrared absorbing agents such as polymethine compounds, cyanine compounds, phthalocyanine compounds, naphthalocyanine compounds, naphthoquinone compounds, anthraquinone compounds, dithiol compounds, immonium compounds, diimonium compounds, aminium compounds, pyrylium compounds, cerylium compounds, squarylium compounds, and counterion bonds between benzenedithiol metal complex anions and cyanine dye cations; inorganic infrared absorbing agents such as tungsten oxide, tin oxide, indium oxide, magnesium oxide, titanium oxide, chromium oxide, zirconium oxide, nickel oxide, aluminum oxide, zinc oxide, iron oxide, ammonium oxide, lead oxide, bismuth oxide, lanthanum oxide, tungsten oxide, indium tin oxide, and antimony tin oxide; and the like. The infrared absorbing agent may be used alone or in combination of two or more. Among the infrared absorbing agents, inorganic infrared absorbing agents are preferred, and indium tin oxide and / or antimony tin oxide are more preferred.

[0290] Indium tin oxide and / or antimony tin oxide are preferred because they have good stability in the coating liquid for forming the organic-inorganic composite anti-fogging film and are more uniformly dispersed in the polyvinyl acetal resin. The infrared absorbing agent is preferably added in an amount of 0.1 to 50 parts by weight, more preferably 1.0 to 40 parts by weight, and even more preferably 2 to 35 parts by weight, based on 100 parts by weight of the water-absorbing resin.

[0291] The first functional layer 2 and the second functional layer 3 do not have to be adjacent to each other. For example, a primer layer or an absorption layer or modification layer that absorbs light of a specific wavelength may be provided between the first functional layer 2 and the second functional layer 3.

[0292] <7.Applications> The cover member according to this embodiment can be used as a cover member for an imaging device provided on an aircraft such as a drone, or as a cover member for a surveillance camera, as in the first embodiment. In particular, when an anti-reflection layer is formed as the second functional layer 3, it can be suitably used as a cover member for an imaging device of an aircraft, which is often photographed outdoors where the environment changes. In particular, when an aircraft suddenly rises, the pressure changes suddenly. As can be understood from Boyle's law, when the pressure decreases, the temperature decreases. Therefore, the transparent laminate with anti-fogging function according to the present invention can be suitably used.

[0293] [Example] Examples 21 to 27 according to the second embodiment will be described below, however, the present invention is not limited to the following examples.

[0294] Example 21 As Example 21, the following cover member was produced. (1) Substrate: Float glass with a thickness of 2.8 mm was used. (2) First functional layer: The anti-fogging layer shown in Example 1 of the first embodiment was formed on the first main surface of the substrate. However, this anti-fogging layer did not have a hydrophilic layer. The film thickness was 8 μm and the refractive index was 1.55. (3) Second functional layer: A single anti-reflection layer as shown below was formed.

[0295] After forming the anti-fog layer, a coating liquid for the anti-reflection layer was prepared as follows. First, 0.6 g of tetraethoxysilane (TEOS) (Tokyo Chemical Industry Co., Ltd.), 1.18 g of methyltriethoxysilane (MTES) (Tokyo Chemical Industry Co., Ltd.), 0.82 g of 0.3 mass% formic acid (Kishida Chemical Co., Ltd.), 3 g of a sol of hollow silica particles (JGC Catalysts and Chemicals Co., Ltd., product name: Sururia 4110, silica solid content: about 25 mass%), and 22.4 g of ethanol (Kishida Chemical Co., Ltd.) were mixed and reacted at 35°C for 3 hours. In this way, a coating liquid for the second functional layer according to Example 22 was obtained. In the sol of hollow silica particles, the average particle diameter of the hollow silica particles was about 50 nm, the thickness of the shell made of silica was 10 to 20 nm, the maximum dimension of the internal space of the hollow silica particles was about 10 to 30 nm, and the refractive index of the hollow silica particles was 1.25. The solid content of this coating liquid contained 0.6 mass% of silica derived from TEOS, 1.6 mass% of polymethylsilsesquioxane derived from MTES, and 2.6 mass% of hollow silica particles. The ratio of the amount of substance of MTES to the amount of substance of TEOS added in the preparation of the liquid composition according to Example 1 was 7 / 3. The ratio of the weight of hollow silica particles to the total weight of the solid content of silica derived from TEOS and polymethylsilsesquioxane derived from MTES was 1.3 / 1.1.

[0296] Next, the coating liquid was applied to the anti-fogging layer by spin coating. Immediately after application, the coating film had a good appearance and was uniform. After that, the coating film was dried in an oven at 200°C for 10 minutes to obtain a cover member according to Example 22.

[0297] The anti-reflection film had a thickness of 100 nm and a refractive index of 1.24±0.5. The volume ratio of the materials constituting the anti-reflection film was as follows: hollow silica particles 50 vol%, binder 23 vol%, and void ratio 23 vol%.

[0298] Example 22 As Example 22, the following cover member was produced. (1) Substrate: Float glass with a thickness of 2.8 mm was used. (2) First functional layer: The anti-fogging layer shown in Example 1 of the first embodiment was formed on the first main surface of the substrate. However, this anti-fogging layer did not have a hydrophilic layer. The film thickness was 8 μm and the refractive index was 1.55. (3) Second functional layer: The following two anti-reflection layers were formed.

[0299] After forming the anti-fog layer, the coating liquid for the anti-reflection layer was prepared as follows. That is, the coating liquid for the first layer was prepared in the same manner as the coating liquid of Example 21, except that the sol of hollow silica particles was not added. Then, this coating liquid was applied onto the anti-fog layer by spin coating. Next, the coating film was dried in an oven at 200°C for 10 minutes to form the first layer. The refractive index of this first layer was 1.46, and the thickness was 90 nm.

[0300] Then, on this first layer, a coating liquid similar to that of Example 21 was applied by spin coating. However, the coating liquid had a higher ratio of hollow silica particles and a higher void ratio than that of Example 21. Next, this coating film was dried in an oven at 200°C for 10 minutes to form a second layer. The refractive index of this second layer was 1.16, and the thickness was 95 nm.

[0301] (Examples 23 to 27) As Examples 23 to 27, the following cover members were produced. (1) Substrate: A Glanova (manufactured by Nippon Sheet Glass Co., Ltd.) having a thickness of 1.1 mm was used. (2) First functional layer: The anti-fogging layer shown in Example 1 of the first embodiment was formed on the first main surface of the substrate. However, this anti-fogging layer did not have a hydrophilic layer. The film thickness was 8 μm and the refractive index was 1.55. (3) Second functional layer: A single anti-reflection layer as shown below was formed.

[0302] After forming the anti-fog layer, a coating liquid for an anti-reflection layer having the composition (unit: mass%) shown in Table 10 was prepared. First, tetraethoxysilane (TEOS) (Tokyo Chemical Industry Co., Ltd.), methyltriethoxysilane (MTES) (Tokyo Chemical Industry Co., Ltd.), 0.3 mass% formic acid (Kishida Chemical Co., Ltd.), hollow silica particle sol (JGC Catalysts and Chemicals Co., Ltd., product name: Sururia 4110, silica solid content: about 25 mass%), solvent, leveling agent, etc. were mixed and reacted at 35°C for 3 hours. In this way, a coating liquid for a second functional layer according to Examples 23 to 27 was obtained. In the hollow silica particle sol, the average particle diameter of the hollow silica particles was about 50 nm, the thickness of the shell made of silica was 10 to 20 nm, the maximum dimension of the internal space of the hollow silica particles was about 10 to 30 nm, and the refractive index of the hollow silica particles was 1.25.

[0303] [Table 10]

[0304] The solvents, leveling agents, etc. shown in Table 10 are as follows. Among them, E to H are high boiling point solvents with boiling points of 100° C. or higher. A: Methanol B: Ethanol C: 2-propanol D: 1-propanol E: 1-butanol F: 1-methoxy-2-propanol G: 3-methoxy-3-methyl-1-butanol H: 3-methoxy-3-methyl-1-butyl acetate MIBK: Methyl isobutyl ketone KP-341: Leveling agent (manufactured by Shin-Etsu Chemical Co., Ltd.) BYK-378_10%: Leveling agent (manufactured by BYK Japan Co., Ltd.)

[0305] Next, the coating solution according to Example 23 was applied to the anti-fog layer by spin coating, and the coating solutions according to Examples 24 to 27 were applied by roll coating. Immediately after application, a uniform coating film with good appearance was obtained. The coating film was then dried in a heating furnace at 120°C for 10 minutes to obtain the cover members according to Examples 24 to 27.

[0306] When breath was blown onto the second functional layers of the cover members of Examples 24 to 27 thus formed, and the anti-fogging performance was evaluated, no fogging occurred in any of the cases.

[0307] Next, the single-sided reflectance of Examples 23 and 26 was measured. The results are shown in FIG. 11. The average visible light reflectance of Examples 23 and 26 was 0.71% and 0.31%, respectively. Although not shown, the reflectance of the cover member having only the anti-fogging layer without the second functional layer was 4 to 5%. Therefore, it was found that the reflectance of the cover members of Examples 23 and 26 could be significantly reduced.

[0308] (Examples 28 to 30) As Examples 28 to 30, the following cover members were prepared. First, an anti-fog film (manufactured by Fujifilm Corporation, model number: MF-600) was prepared. This film is a TAC (triacetyl cellulose) film having a modified layer (anti-fog layer) exhibiting anti-fog properties by modifying the surface of the TAC film, and a PET film, which are integrated by bonding them together via an adhesive layer. Specifically, a film having the following configuration was prepared. Protective film (PE: 60 μm) / TAC modified layer (5 μm) / TAC (120 μm) / adhesive layer (15 μm) / PET (50 μm) / adhesive layer (25 μm) / protective film (PET: 38 μm).

[0309] Next, the protective film (PE: 60 μm) on the TAC modified layer side was peeled off, and the surface of the TAC modified layer was corona discharge treated (manufactured by Shinko Electric Instrumentation Co., Ltd., model number: Corona Master PS-1M, 14.5 kW). The coating solution of Example 21 was applied to the corona discharge treated surface by spin coating (5000 rpm, 20 seconds, room temperature) (Example 28). The treatment was performed for 10 minutes at a baking temperature of 120 ° C. The single-sided reflectance of the surface on which the anti-reflection layer was formed was measured using a reflectance measuring device (manufactured by Olympus Corporation, model number: USPM-RU III). This device allows for highly accurate spectral reflectance measurement without being affected by the backside reflected light. The refractive index calculated from the reflectance obtained by the reflectance measuring device was 1.2382, and the film thickness was 107 nm (Table 11). Furthermore, the rotation speed of the spin coater was changed to form anti-reflection layers with different film thicknesses on the film (Example 29, Example 30).

[0310] As described above, after forming an anti-reflection film on the TAC modified layer (anti-fogging layer), the protective film (PET: 38 μm) on the adhesive layer side was peeled off, and the adhesive layer surface was attached to a glass substrate (manufactured by Nippon Sheet Glass Co., Ltd., product name: Glanova, thickness: 2.1 mm). In this way, the cover members according to Examples 28 to 30 were completed. Then, they were evaluated as follows. [Table 11]

[0311] The single-sided reflectance in the range of 400 to 700 nm of the films on which the antireflection coatings of Examples 28 to 30 were formed is shown in Figure 12. The single-sided reflectance in the range of 400 to 700 nm without the antireflection coating is shown as the film without the antireflection layer. As is clear from Figure 12, when the antireflection coating of the present invention is not formed, that is, when the antifogging layer (TAC modified layer) is formed, as in Examples 28 to 30, the single-sided reflectance in the range of 400 to 700 nm is less than 1%, and a significant antireflection effect is observed.

[0312] Furthermore, when breath was blown onto the anti-fogging layers on which the antireflection films of Examples 28 to 30 were formed, and the anti-fogging performance was evaluated, no fogging occurred in any of the cases.

[0313] <C. Modified Example> As described above, the embodiments of the present invention have been explained. However, the present invention is not limited to the above embodiments, and various modifications are possible without departing from the gist thereof. The following modified examples can be combined as appropriate.

[0314] <1> The base material 1 may be a composite material of a resin material and a glass plate, or may be a laminated glass in which an intermediate film is sandwiched between two glass plates.

[0315] <2> The base material 1 may be, for example, a mirror having an antiglare layer (or a surface subjected to antiglare treatment).

[0316] In the case of a mirror, peeling of the film often occurs at the location where the user touches it, and it is often used for a long period of time. Durability against peeling of the surface film is required. Therefore, as described above, when the antifogging layer is directly applied to the mirror which is the base material, the base material (glass plate) and the antifogging layer are firmly bonded by a siloxane bond, so high durability can be expected even in long-term use.

[0317] In addition, when a mirror is used in a bathroom or a washstand, it is in a particularly high-humidity environment, so high antifogging performance is required. On the other hand, if the antifogging layer only has water absorption performance, when the saturation amount is exceeded, water droplets will occur on the surface of the antifogging layer, which will cause fogging. Therefore, if the hydrophilic layer as described above is formed on the surface of the antifogging layer, when the moisture absorption layer is saturated, a water film will occur on the surface. Therefore, even in a high-humidity environment, it is possible to avoid the image from becoming invisible due to fogging. Note that the occurrence of a water film means that the contact angle of water becomes 20 degrees or less. Also, not only the hydrophilic layer but also a water-repellent layer may be provided. Here, the water-repellent layer refers to a layer in which the contact angle of water becomes 90 degrees or less.

[0318] When a mirror is used as the substrate, it is preferable to laminate an anti-fog layer that does not have a substrate film such as PET. Without a substrate film, distortion caused by the substrate film can be prevented. In particular, in the case of a mirror, clarity of the image and high low distortion are required. In addition, in a mirror, incident light and reflected light pass through the anti-fog layer. That is, since light passes through the anti-fog layer twice, an anti-fog layer that does not have a substrate film is advantageous in terms of distortion. In addition, when the anti-fog layer has a certain thickness such as 1 to 20 μm, the bending rigidity is 1 to 4 GPa, so that it can be handled even without a substrate film such as PET. In addition, an anti-fog layer with high tensile strength can be preferably used.

[0319] <3> In the above second embodiment, an example in which the second functional layer, which is an anti-reflection layer, is laminated on the first functional layer is shown, but such an anti-reflection layer can also be laminated directly on the substrate 1 as the first functional layer. In this case, in addition to directly laminating the first functional layer on the substrate, a sheet material in which an adhesive layer, a substrate sheet, and the first functional layer are laminated in this order can be prepared, and the adhesive layer can be attached to the substrate. In this case, the substrate sheet can be formed of, for example, polyethylene terephthalate, polyvinyl chloride, polyvinylidene chloride, polycarbonate, or an acrylic resin. In addition, the adhesive layer may be any material that can fix the substrate sheet to the substrate 1 with sufficient strength. Specifically, an adhesive layer such as an acrylic, rubber, or resin copolymerized with a methacrylic and acrylic monomer having tackiness at room temperature and set to a desired glass transition temperature can be used. The anti-reflection layer can contain the following second solvent whose boiling point is higher than the boiling point of water and lower than the heat resistance temperature of the substrate sheet.

[0320] The first functional layer, which is an anti-reflection layer, can also be formed of two layers, that is, it can have the same structure as the second functional layer 3 described with reference to FIG. [Explanation of symbols]

[0321] 1 Board 11 First main surface 12 Second main surface 2 First functional layer 3 Second functional layer

Claims

1. a transparent substrate having a first major surface and a second major surface; A transparent first functional layer laminated on a first main surface of the substrate; A transparent laminate comprising:

2. The transparent laminate according to claim 1 , wherein the first functional layer has an anti-fogging function.

3. The transparent laminate according to claim 1 or 2, wherein the surface roughness Ra of the first functional layer is 1 to 1000 nm.

4. The first functional layer is A base film having a first main surface and a second main surface; An adhesive layer laminated on the second main surface of the base film; An anti-fogging layer laminated on a first main surface of the substrate film; Equipped with The transparent laminate according to claim 1 , wherein the base film is fixed to the first main surface of the substrate via the adhesive layer.

5. The first functional layer includes an adhesive layer and an anti-fogging layer, The transparent laminate according to claim 1 , wherein the anti-fogging layer is fixed to the first main surface of the substrate via the adhesive layer.

6. The first functional layer comprises an anti-fogging layer; The transparent laminate according to claim 1 , wherein the anti-fogging layer is laminated on the first main surface of the substrate.

7. The transparent laminate according to claim 4 , wherein the antifogging layer has a moisture absorbing layer containing a moisture absorbing resin material.

8. The transparent laminate according to claim 7 , wherein the antifogging layer comprises the moisture absorbing layer and a hydrophilic layer laminated on the moisture absorbing layer and having hydrophilic properties.

9. The transparent laminate according to claim 8 , wherein the hydrophilic layer of the anti-fogging layer contains a polyether-modified dimethylsiloxane represented by the following formula (A): 【Chemistry 1】 wherein m is an integer of 2 or more, n, x, and y are independently integers of 1 or more; R 1 is a hydrogen atom or a methyl group, R 2 is an alkyl group having 1 to 3 carbon atoms.

10. In the formula (A), m is an integer from 1 to 3; n is an integer from 3 to 600, y / (x+y) is 0.01 or more and less than 1; The transparent laminate according to claim 9, wherein the average molecular weight is from 3,000 to 300,000.

11. The transparent laminate according to claim 7 , wherein in the antifogging layer, a hydrophilizing agent is dispersed in the moisture absorbing layer.

12. The transparent laminate according to claim 11 , wherein the anti-fogging layer contains a solvent having a boiling point of 100° C. or more and 300° C. or less.

13. The transparent laminate according to claim 12 , wherein the solvent has an alcohol group.

14. 14. The transparent laminate according to claim 11, wherein the anti-fogging layer has anti-fogging properties after the anti-fogging layer is abraded a predetermined number of times with a cloth soaked in alcohol.

15. The transparent laminate according to claim 11 , wherein the anti-fogging layer has anti-fogging properties after a predetermined constant temperature and humidity test.

16. The transparent laminate according to claim 11 , wherein the antifogging layer is formed of a single layer.

17. The transparent laminate according to claim 1 , wherein the first functional layer is mainly composed of an inorganic compound.

18. The visible light transmittance is 85% or more, The transparent laminate according to claim 17, which has a visible light reflectance of 10% or less.

19. 19. The transparent laminate according to claim 17 or 18, wherein the minimum value of the transmittance in the visible light wavelength range is within 5% of the transmittance of the substrate.

20. 20. The transparent laminate according to claim 17, wherein the maximum reflectance in the visible light wavelength range is within 5% of the reflectance of the substrate.

21. Regarding reflectance in the visible light wavelength range, The transparent laminate according to any one of claims 17 to 20, which satisfies 1 ? maximum reflectance / minimum reflectance ? 1.

5.

22. The transparent laminate according to claim 17 , wherein the first functional layer contains inorganic fine particles and an inorganic binder.

23. The transparent laminate according to claim 22 , wherein the film thickness of the first functional layer is not more than twice the particle diameter of the inorganic fine particles.

24. The inorganic fine particles are SiO 2 The transparent laminate according to claim 22 or 23, which is formed by

25. The SiO in the first functional layer 2 The transparent laminate according to claim 24, wherein the content of is 28 mass % or less.

26. The transparent laminate according to claim 22 , wherein the first functional layer contains photocatalytic fine particles.

27. 27. The transparent laminate according to claim 26, wherein the photocatalyst particles are formed of an oxide or an oxynitride containing any one of titanium, tungsten, and iron as a main component.

28. The transparent laminate according to claim 26 or 27, wherein the content of the photocatalyst particles is 40 mass % or less.

29. The transparent laminate according to claim 26 , wherein the content of the inorganic binder is 30% by mass or more.

30. 30. A transparent laminate according to any one of claims 17 to 29, wherein the first functional layer has anti-fogging properties after being immersed in water for a predetermined period of time.

31. A transparent laminate described in any one of claims 17 to 30, wherein the first functional layer has anti-fogging properties after the first functional layer is abraded a predetermined number of times with a cloth soaked in alcohol.

32. A transparent laminate described in any one of claims 17 to 31, wherein the first functional layer has anti-fogging properties by abrading the first functional layer a predetermined number of times with a cloth soaked in alcohol and then irradiating it with ultraviolet light.

33. 33. A transparent laminate according to claim 17, wherein the first functional layer has anti-fogging properties when irradiated with ultraviolet light after a predetermined constant temperature and humidity test.

34. The transparent laminate according to any one of claims 17 to 33, which is used as a cover member for a surveillance camera that is placed outdoors.

35. The transparent laminate according to claim 34, wherein the surveillance camera is equipped with an ultraviolet irradiation device.

36. The transparent laminate according to claim 34 or 35, wherein the first functional layer is arranged to face the surveillance camera.

37. The transparent laminate according to claim 34 , wherein the first functional layer is positioned facing away from the surveillance camera.

38. The transparent laminate according to claim 2 , further comprising a second functional layer laminated on the first functional layer and having moisture permeability.

39. the first functional layer is formed of an organic-inorganic composite material, The transparent laminate according to claim 38 , wherein the refractive index of the second functional layer is smaller than that of the first functional layer.

40. The transparent laminate according to claim 38 or 39, wherein the second functional layer is a single layer.

41. The transparent laminate according to claim 40, wherein the refractive index of the second functional layer is 1.10 to 1.

45.

42. The transparent laminate according to claim 41 , wherein when the refractive index of the first functional layer is X, the refractive index of the second functional layer is √X±0.

1.

43. The transparent laminate according to claim 42 , wherein the second functional layer contains hollow particles and a binder that binds the hollow particles.

44. The transparent laminate according to claim 43, wherein the hollow particles have a refractive index of 1.15 to 2.

70.

45. The transparent laminate according to claim 43 or 44, wherein the hollow particles have an average particle size of 20 to 100 nm.

46. 46. ​​The transparent laminate according to any one of claims 43 to 45, wherein the hollow particles are selected from the group consisting of silica, magnesium fluoride, alumina, aluminosilicate, titania, and zirconia.

47. 47. The transparent laminate according to claim 38, wherein the second functional layer contains a solvent having a boiling point of 100°C or higher and 300°C or lower.

48. The transparent laminate according to claim 47, wherein the solvent is mainly composed of 3-methoxy-3-methyl-1-butanol.

49. The second functional layer contains the solvent at 1 ppb or more and 5 g / cm 3 49. The transparent laminate according to claim 47 or 48, comprising:

50. 50. The transparent laminate according to any one of claims 43 to 49, wherein the binder contains at least one of polysilsesquioxane and silica.

51. A transparent laminate according to any one of claims 43 to 50, wherein the void ratio of the second functional layer is 0 to 70 vol%.

52. A transparent laminate as described in claim 38 or 39, wherein the second functional layer comprises a first layer laminated on the first functional layer, and a second layer laminated on the first layer and having a lower refractive index than the first layer.

53. The refractive index of the first layer is 1.35 to 1.55; The transparent laminate according to claim 52, wherein the second layer has a refractive index of 1.10 to 1.

25.

54. The transparent laminate according to claim 53, wherein the second layer contains hollow particles and a binder that binds the hollow particles.

55. The transparent laminate according to claim 54, wherein the hollow particles have a refractive index of 1.15 to 2.

70.

56. The transparent laminate according to claim 54 or 55, wherein the hollow particles have an average particle size of 20 to 100 nm.

57. 57. The transparent laminate according to any one of claims 54 to 56, wherein the hollow particles are selected from the group consisting of silica, magnesium fluoride, alumina, silicate of aluminum, titania, and zirconia.

58. 58. The transparent laminate according to any one of claims 54 to 57, wherein the binder contains at least one of polysilsesquioxane and silica.

59. The transparent laminate according to any one of claims 54 to 58, wherein the second layer has a void ratio of 0 to 70 vol%.

60. 60. The transparent laminate according to any one of claims 54 to 59, wherein the first layer contains the binder of the second layer.

61. A transparent laminate described in any one of claims 38 to 60, wherein the flexural modulus of the second functional layer is 1 to 10 GPa.

62. 62. A transparent laminate according to any one of claims 38 to 61, wherein the flexural modulus of the second functional layer overlaps with the flexural modulus of the first functional layer.

63. 63. A transparent laminate according to any one of claims 38 to 62, wherein the difference between the linear expansion coefficient of the first functional layer and the linear expansion coefficient of the second functional layer is 50 ppm / °C or less.

64. The transparent laminate according to claim 1 , wherein the first functional layer has an anti-reflection function.

65. The transparent laminate according to claim 64, wherein the first functional layer is formed of a film in which an adhesive layer, a base sheet, and an anti-reflection layer are laminated in this order.

66. The transparent laminate according to claim 65, wherein the refractive index of the anti-reflection layer of the first functional layer is 1.10 to 1.

45.

67. 67. The transparent laminate according to claim 65 or 66, wherein the antireflection layer of the first functional layer contains hollow particles and a binder that binds the hollow particles.

68. The transparent laminate according to claim 67, wherein the hollow particles have a refractive index of 1.15 to 2.

70.

69. The transparent laminate according to claim 67 or 68, wherein the hollow particles have an average particle size of 20 to 100 nm.

70. 70. The transparent laminate according to any one of claims 65 to 69, wherein the antireflection layer contains a second solvent having a boiling point higher than that of water and lower than or equal to the heat resistance temperature of the substrate.

71. The transparent laminate according to claim 70, wherein the second solvent is mainly composed of 3-methoxy-3-methyl-1-butanol.

72. The first functional layer contains the second solvent at a concentration of 1 ppb or more and 5 g / cm 3 % or less. The transparent laminate according to claim 70 or 71.

73. 73. The transparent laminate of claim 2, wherein the substrate is glass.

74. 74. The transparent laminate according to claim 2, wherein the substrate is float glass produced by a float process, and the concentration of tin oxide in the first main surface is lower than the concentration of tin oxide in the second main surface.

75. 74. The transparent laminate according to claim 2, wherein the substrate is float glass produced by a float process, and the concentration of tin oxide in the first main surface is higher than the concentration of tin oxide in the second main surface.

76. A transparent laminate described in any one of claims 1 to 75, further comprising a third functional layer laminated on the second main surface of the substrate.

Citation Information

Patent Citations

  • It is alert with waterproof unmanned aerial vehicle of antifog smoke protection

    CN205524925U

  • Coating agent excellent in antifogging properties

    JP1994306327A

  • Member having hydrophilicity

    JP2015210495A

  • Glass plate production method and automobile glass plate

    JP2018108677A

  • Antifogging agent composition

    JP2018150470A